Polarizing film laminate for power running vehicle, and optical display panel using the polarizing film laminate

By adjusting the iodine concentration of the polarizing film and the moisture content of the polarizing film laminate to ensure their combination within a specific range, the polyolefinization, decolorization and heating reddening of optical display panels in powered vehicles in high-temperature or high-humidity environments are solved. problem, achieving long-term durability and stable performance.

CN114839711BActive Publication Date: 2025-01-24NITTO DENKO CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202210355297.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-02-28
Filing Date
2019-02-28
Publication Date
2025-01-24
Estimated Expiration
2039-02-28

AI Technical Summary

Technical Problem

The optical display panel in a powered vehicle is prone to polyalkylation, decolorization and heating red change in high temperature or high humidity environments, resulting in performance deterioration or failure.

Method used

By adjusting the iodine concentration of the polarizing film and the moisture content of the polarizing film laminate, a combination within a specific range is ensured. For example, the first coordinate point connecting the iodine concentration of 7.0 wt.% and the moisture content of 0.7 g/m2 and the iodine concentration of 2.2 wt.% and the moisture content of 3.2g/m2 in the area of ​​the second coordinate point to comprehensively solve the problems of polyeneization, decolorization and heating reddening.

Benefits of technology

Effectively solve the problem of polymerization, discoloration and heating red changes in high temperature or high humidity environment, and ensure the long -term durability and stability of the optical display panel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114839711B_ABST
    Figure CN114839711B_ABST
Patent Text Reader

Abstract

The present invention provides a polarizing film laminate that can comprehensively solve the problems of polyeneization, discoloration and red discoloration upon heating. In an x-y orthogonal coordinate system where the iodine concentration of the polarizing film is taken as the x-axis and the moisture content of the polarizing film laminate is taken as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region: the region is composed of a connection between an iodine concentration of 7.0 wt.% and a moisture content of 0.7 g / m 2 The first coordinate point and iodine concentration 2.2wt.% and moisture content 3.2g / m 2 The first line segment of the second coordinate point, connecting the second coordinate point and the iodine concentration of 2.2wt.% and the moisture content of 4.0g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 3.0wt.% and the water content of 4.0g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 10.0wt.% and the water content of 0.7g / m 2 It is surrounded by a fourth line segment of the fifth coordinate point and a fifth line segment connecting the first coordinate point and the fifth coordinate point.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on February 28, 2019, with application number 201980015811.X and invention name “Polarizing film laminate for power running vehicle, and optical display panel using the same”. Technical Field

[0002] The present invention relates to a polarizing film laminate, and more particularly to a polarizing film laminate used for an optical display panel mounted on a body of a power vehicle, and an optical display panel using the polarizing film laminate. Background Art

[0003] In recent years, optical display panels such as liquid crystal panels and organic EL panels have been used in electronic devices such as smartphones and personal computers, and electrical products such as IoT home appliances. In addition, various possibilities have been found for their use in powered vehicles such as automobiles, trains, and airplanes. For example, it is conceivable to mount optical display panels on the windshield, dashboard, exterior, and other various parts of the vehicle body to provide various information to the driver and to transmit various information to the outside.

[0004] However, unlike smart phones, in most cases, power vehicles are used in harsh outdoor environments. The performance of optical display panels, especially polarizing film stacks (polarizers) used for optical display panels, and polarizing films (polarizers) used for polarizing film stacks may deteriorate due to usage environments such as high temperature or high humidity. In the worst case, they may even become unusable.

[0005] Patent Document 1 discloses an example of a polarizer having improved durability in a high temperature or high humidity environment, a polarizing plate using the polarizer, and a liquid crystal display device using the polarizing plate. As durability, red leakage (depolarization of long wavelength light) under crossed Nicols that occurs when placed under high temperature conditions is considered a problem, and in order to solve this problem, a scheme is proposed in which zinc is contained and the relationship between the zinc content and the iodine content is adjusted to a given range.

[0006] Similarly, Patent Document 2 relates to a polarizing plate for an in-vehicle image display device having improved durability in a high temperature or high humidity environment, wherein attention is paid to the moisture content of the polarizing plate and the saturated water absorption of the protective film. In-vehicle polarizing plates are required to have high temperature durability, but in a high temperature environment, the transmittance of the polarizing plate may be significantly reduced due to polyeneization. In order to solve this problem, Patent Document 2 proposes a solution of using a transparent protective film having a saturated water absorption within a given range as a transparent protective film bonded to a polarizer and reducing the moisture content of the polarizing plate.

[0007] Patent Document 3 also relates to a polarizing plate with improved durability under high temperature or high humidity, and focuses on the moisture content of the polarizing plate and the moisture permeability of the protective film. In a high temperature environment, the interior of the polarizing plate reaches a high temperature and high humidity state, resulting in a large change in transmittance, polarization degree, image hue, etc., and a decrease in reliability as a polarizing plate. Therefore, the patent document proposes a solution of attaching a protective film with low moisture permeability while reducing the moisture content of the polarizer as much as possible.

[0008] Prior art literature

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2003-29042

[0011] Patent Document 2: Japanese Patent Application Publication No. 2014-102353

[0012] Patent Document 3: Japanese Patent Application Publication No. 2002-90546 Summary of the invention

[0013] Problems to be solved by the invention

[0014] Regarding optical display panels, especially polarizing film laminates used in optical display panels and polarizing films used in polarizing film laminates, "polyeneization", "discoloration", and "heat reddening" are known as problems that may occur in high temperature or high humidity environments.

[0015] Generally speaking, "polyeneization" refers to the phenomenon that the monomer transmittance of a polarizing film stack decreases due to being placed in a high temperature or high humidity environment. In addition, "discoloration" and "heat reddening" are also the phenomena that the orthogonal transmittance decreases when the polarizing film stack is arranged in an orthogonal Nicol manner and the orthogonal transmittances at wavelengths of 410nm and 700nm are measured due to being placed in a high temperature or high humidity environment. Among them, "discoloration" is particularly known as the phenomenon of increase in transmittance on the long wavelength side of about 700nm and the short wavelength side of about 410nm, and discoloration occurring under black display. On the other hand, "heat reddening" is particularly known as the phenomenon of increase in transmittance on the long wavelength side of about 700nm and change of color of the polarizing film to red.

[0016] Patent Document 1 mainly focuses on the problem of "decolorization", Patent Document 2 mainly focuses on the problem of "polyeneization", and Patent Document 3 mainly focuses on the problem of "red discoloration upon heating". It can be considered that the solutions proposed in each document are at least effective in solving their respective problems. However, the inventions recorded in each patent document may not be sufficient to solve these problems in a comprehensive manner. "Polyeneization", "decolorization", and "red discoloration upon heating" are all related to each other through iodine and moisture, and further through temperature and humidity that affect moisture. Based on this fact, the applicant of the present application has repeatedly conducted in-depth research and obtained the following insights: By adjusting the iodine concentration of the polarizing film and the moisture content of the polarizing film laminate, these problems can be solved in a comprehensive manner. The purpose of the present invention is to solve the above three problems in a comprehensive manner by seeking to adjust the iodine concentration of the polarizing film and the moisture content of the polarizing film laminate.

[0017] Solutions to the problem

[0018] In order to solve the above-mentioned problems, a polarizing film laminate according to one embodiment of the present invention is a polarizing film laminate for an optical display panel installed on a body of a power vehicle, comprising: a polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film directly or through other optical films bonded to at least one side of the polarizing film, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis, the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region, which is composed of a connected iodine concentration of 7.0 wt.% and a moisture content of 0.7 g / m 2 The first coordinate point and iodine concentration 2.2wt.% and moisture content 3.2g / m 2 The first line segment of the second coordinate point of the iodine concentration of 2.2wt.% and the water content of 4.0g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 3.0wt.% and the water content of 4.0g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 10.0wt.% and the water content of 0.7g / m 2 The fourth line segment of the fifth coordinate point and the fifth line segment connecting the first coordinate point and the fifth coordinate point are surrounded by the fourth line segment.

[0019] According to the polarizing film laminate of this embodiment, the problems of "polyeneization", "discoloration", and "reddening due to heating" can be solved comprehensively.

[0020] In the polarizing film laminate of the above embodiment, the polarizing film may have a thickness of 4 to 20 μm.

[0021] In addition, a polarizing film laminate according to another embodiment of the present invention is a polarizing film laminate for an optical display panel installed on a body of a power vehicle, comprising: a polarizing film formed of a polyvinyl alcohol-based resin, and an optically transparent polarizing film protective film bonded to at least one side of the polarizing film directly or via other optical films, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis, the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region, which is composed of a connected iodine concentration of 4.5 wt.% and a moisture content of 2.0 g / m 2 The sixth coordinate point and iodine concentration 2.2wt.% and moisture content 3.2g / m 2 The sixth line segment of the second coordinate point of the iodine concentration of 2.2wt.% and the water content of 4.0g / m 2 The second line segment of the third coordinate point, connecting the third coordinate point and the iodine concentration of 3.0wt.% and the water content of 4.0g / m 2 The third line segment of the fourth coordinate point, connecting the fourth coordinate point and the iodine concentration of 4.5wt.% and the water content of 3.3g / m 2 It is surrounded by a seventh line segment of the seventh coordinate point and an eighth line segment connecting the sixth coordinate point and the seventh coordinate point.

[0022] In the polarizing film laminate of the above embodiment, the sixth coordinate point may have an iodine concentration of 4.0 wt.% and a water content of 2.3 g / m 2 The seventh coordinate point has an iodine concentration of 4.0 wt.% and a water content of 3.5 g / m 2 The coordinate point of .

[0023] In the polarizing film laminate of the above embodiment, the film thickness of the polarizing film may be 11 to 20 μm.

[0024] Another embodiment of the polarizing film laminate of the present invention is a polarizing film laminate for an optical display panel installed on a body of a powered vehicle, comprising: a polarizing film formed of a polyvinyl alcohol-based resin, and an optically transparent polarizing film protective film bonded to at least one side of the polarizing film directly or via other optical films, wherein the iodine concentration (wt.%) of the polarizing film is taken as the x-axis, the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a moisture content within the following region, which is composed of a connected iodine concentration of 7.0 wt.% and a moisture content of 0.7 g / m 2 The first coordinate point and iodine concentration 3.0wt.% and water content 2.6g / m2 The eleventh line segment of the eighth coordinate point, connecting the eighth coordinate point and the iodine concentration of 6.0wt.% and the water content of 2.6g / m 2 The tenth line segment of the ninth coordinate point connects the ninth coordinate point and the iodine concentration of 10.0wt.% and the water content of 0.7g / m 2 The fifth coordinate point is surrounded by a twelfth line segment and a fifth line segment connecting the first coordinate point and the fifth coordinate point.

[0025] According to the polarizing film laminate of this embodiment, the problems of "polyeneization", "discoloration", and "reddening due to heating" can be solved comprehensively.

[0026] In the polarizing film laminate of the above embodiment, the eighth coordinate point may be 4.5 wt.% iodine concentration and 2.0 g / m 2 The sixth coordinate point, the ninth coordinate point is iodine concentration 7.2wt.% and water content 2.0g / m 2 The tenth coordinate point.

[0027] In the polarizing film laminate of the above embodiment, the polarizing film may have a thickness of 4 to 11 μm.

[0028] Moreover, in the polarizing film laminated body of the said embodiment, it is preferable that the said polarizing film contains zinc.

[0029] Furthermore, in the polarizing film stack of the above-mentioned embodiment, for a sample composed of a polarizing film stack and glass plates laminated on both sides of the polarizing film stack via an adhesive, the monomer transmittance after heating at 95°C / 500 hours is the same as or greater than the monomer transmittance before heating.

[0030] Thereby, the problem of polyeneization can be effectively solved.

[0031] Preferably, in the polarizing film laminate of the above-mentioned embodiment, for a sample composed of a polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, the change in the orthogonal transmittance at a wavelength of 410 nm caused by a heat treatment at 95°C / 500 hours is less than 1%, and the change in the orthogonal transmittance at a wavelength of 700 nm is less than 5%.

[0032] Thereby, the problem of discoloration can be effectively solved.

[0033] Preferably, in the polarizing film laminate of the above-mentioned embodiment, for a sample composed of a polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, the change in the orthogonal transmittance at a wavelength of 410 nm caused by a heat treatment at 95°C / 500 hours is greater than 1%, and the change in the orthogonal transmittance at a wavelength of 700 nm is less than 5%.

[0034] Thereby, the problem of reddening due to heating can be effectively solved.

[0035] In the polarizing film laminate of the above embodiment, an antireflection layer may be provided on the visible side of the polarizing film via a substrate, and the moisture permeability of the antireflection film including the substrate and the antireflection layer is 15 g / m 2 ·More than 24h.

[0036] Furthermore, in the polarizing film laminate of the above embodiment, it is preferred that:

[0037] A liquid crystal cell having a liquid crystal layer including liquid crystal molecules oriented in one direction in a plane in a state where no electric field is applied;

[0038] a first polarizing film disposed on one side of the liquid crystal unit; and

[0039] A second polarizing film is disposed on the other side of the liquid crystal unit in a manner such that its absorption axis is orthogonal to the absorption axis of the first polarizing film.

[0040] Between the first polarizing film and the liquid crystal unit, a first phase difference layer and a second phase difference layer are sequentially arranged from one side of the first polarizing film. When the refractive index of the first phase difference layer in the slow axis x direction within the plane is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer satisfies the relationship of nx1>ny1>nz1. When the refractive index of the second phase difference layer in the slow axis x direction within the plane is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer satisfies the relationship of nz2>nx2≥ny2.

[0041] Furthermore, in the polarizing film laminate of the above embodiment, it is preferred that:

[0042] A liquid crystal cell having a liquid crystal layer including liquid crystal molecules oriented in one direction in a plane in a state where no electric field is applied;

[0043] a first polarizing film disposed on one side of the liquid crystal unit; and

[0044] A second polarizing film is disposed on the other side of the liquid crystal unit in a manner such that its absorption axis is orthogonal to the absorption axis of the first polarizing film.

[0045] Between the first polarizing film and the liquid crystal unit, a first phase difference layer and a second phase difference layer are sequentially arranged from one side of the first polarizing film. When the refractive index of the first phase difference layer in the slow axis x direction within the plane is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer satisfies the relationship of nz1>nx1=ny1. When the refractive index of the second phase difference layer in the slow axis x direction within the plane is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer satisfies the relationship of nx2>ny2=nz2.

[0046] Furthermore, it is preferred that the polarizing film laminate of the above embodiment comprises:

[0047] A liquid crystal cell comprising a liquid crystal layer including liquid crystal molecules oriented in one direction within a plane in a state where no electric field is applied; and

[0048] A polarizing film is disposed on one side of the liquid crystal unit.

[0049] A phase difference layer is arranged between the above-mentioned polarizing film and the above-mentioned liquid crystal unit. When the refractive index in the slow axis x direction within the plane of the phase difference layer is set to nx, the refractive index in the fast axis direction is set to ny, and the refractive index in the thickness z direction is set to nz, the phase difference layer satisfies the relationship nx>nz>ny.

[0050] Furthermore, in order to solve the above-mentioned problems, an optical display panel of one embodiment of the present invention is an optical display panel installed on the body of a power-driven vehicle, comprising: an optical display unit, a polarizing film stack as described in any of the above items joined to one side of the above-mentioned optical display unit directly or via other optical films, and an optically transparent cover plate arranged along the above-mentioned polarizing film stack on the side opposite to the above-mentioned optical display unit, the above-mentioned optical display unit, the above-mentioned polarizing film stack and the above-mentioned transparent cover plate are bonded together by a transparent adhesive layer filled between them with no gaps.

[0051] In the optical display panel of the above embodiment, the transparent cover plate may have a function of a capacitive touch sensor.

[0052] In the optical display panel of the above embodiment, an ITO layer serving as a constituent element of a capacitive touch sensor may be provided between the transparent cover plate and the polarizing film laminate.

[0053] Effects of the Invention

[0054] According to the present invention, the problems of "polyeneization", "bleaching" and "reddening by heating" can be solved comprehensively. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 is a schematic diagram showing the layer structure of an optical display panel.

[0056] Figure 2 This is a diagram for explaining an example of a method for producing a polarizing film.

[0057] Figure 3 This is a diagram showing a calibration curve for calculating the iodine concentration of a polarizing film.

[0058] Figure 4 It is a figure which shows the structure used for reliability test.

[0059] Figure 5 This is a graph in which the results of Examples and Comparative Examples are plotted.

[0060] Figure 6 It is a schematic diagram showing an example of the layer structure of a polarizing film laminate to which an antireflection function is added.

[0061] Figure 7 Schematic diagram showing an example of the layer structure of an optical display panel to which a phase difference layer based on two-plate compensation is added.

[0062] Figure 8 Schematic diagram showing an example of the layer structure of an optical display panel to which a phase difference layer based on monolithic compensation is added.

[0063] Explanation of symbols

[0064] 1 Optical display panel

[0065] 10 Optical display unit

[0066] 11. Transparent adhesive

[0067] 12 Polarizing film laminate

[0068] 13. Transparent adhesive

[0069] 14 Transparent cover

[0070] 120 polarizing film

[0071] 121 Polarizing film protective film

[0072] 122 Polarizing film protective film DETAILED DESCRIPTION

[0073] Hereinafter, a preferred embodiment of the present invention will be described with reference to the accompanying drawings. For the convenience of description, only the preferred embodiment is shown, but the present invention is of course not limited to this.

[0074] The present invention is directed to an optical display panel, in particular an optical display panel mounted on the body of a car, a train, an airplane, or other powered vehicle, and a polarizing film laminate for use with the optical display panel. Here, "mounted on the body" does not necessarily refer only to the case where the optical display panel or polarizing film laminate is fixed to the body, but also includes the case where, for example, the optical display panel or polarizing film laminate used in a smart phone or the like is freely mounted or brought into a powered vehicle. In other words, "mounted on the body" includes all situations where the optical display panel or polarizing film laminate is used together with a powered vehicle and may be exposed to a high temperature or high humidity environment.

[0075] 1. Optical display panel

[0076] Figure 1 An example of the layer structure of the optical display panel 1 is shown in a schematic diagram. The optical display panel 1 includes at least: an optical display unit 10, a polarizing film laminate 12 laminated on one side 10a (visible side) of the optical display unit 10, and an optically transparent cover plate 14 arranged along the polarizing film laminate 12 on the side opposite to the optical display unit 10, i.e., the visible side. On the other side 10b of the optical display unit 10, another polarizing film laminate 17 is arranged via a transparent adhesive 16. The optical display unit 10, the polarizing film laminate 12, and the cover plate 14 are bonded together by layers of transparent adhesive 11 and 13 filled therebetween in a state without gaps. It should be noted that in this specification, unless otherwise specified, the term "bonding" includes adhesion (pressure-sensitive bonding). The optical display unit 10 and the polarizing film laminate 12 may be directly bonded together by the transparent adhesive 11, but may also be bonded together via other optical films (not shown) such as a retardation film and a viewing angle compensation film as required.

[0077] 1-1. Optical display unit

[0078] Examples of the optical display unit 10 include a liquid crystal unit and an organic EL unit.

[0079] As the organic EL unit, an organic EL unit in which a transparent electrode, an organic light-emitting layer and a metal electrode are sequentially stacked on a transparent substrate to form a light-emitting body (organic electroluminescent light-emitting body) can be suitably used. The organic light-emitting layer is a laminate of various organic thin films, and can adopt various layer structures, including, for example: a laminate of a hole injection layer made of a triphenylamine derivative and a light-emitting layer made of a fluorescent organic solid such as anthracene, a laminate of these light-emitting layers and an electron injection layer made of a perylene derivative, or a laminate of a hole injection layer, a light-emitting layer and an electron injection layer.

[0080] As the liquid crystal cell, any of a reflective liquid crystal cell utilizing external light, a transmissive liquid crystal cell utilizing light from a light source such as the backlight 18, and a semi-transmissive and semi-reflective liquid crystal cell utilizing both light from the outside and light from the light source can be used. In the case where the liquid crystal cell is a liquid crystal cell utilizing light from a light source, such as Figure 1 As shown, a polarizing film laminate 17 may also be arranged on the side opposite to the visible side of the optical display unit (liquid crystal unit) 10, and a light source 18 such as a backlight may be arranged. The polarizing film laminate 17 on the light source side and the liquid crystal unit 10 are bonded together via a layer of a suitable transparent adhesive 17. As a driving mode of the liquid crystal unit, any type of mode such as VA mode, IPS mode, TN mode, STN mode, bend orientation (π type) may be adopted.

[0081] 1-2. Cover

[0082] As examples of the cover plate 14, a transparent plate (window layer), a touch panel, etc. can be cited. As a transparent plate, a transparent plate with suitable mechanical strength and thickness can be used. As such a transparent plate, a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate, etc. can be used. For example, a low-reflection film (not shown) can be used to apply a low-reflection treatment to the surface of the cover plate 14. As a touch panel, various touch panels such as a resistive film method, an electrostatic capacitance method, an optical method, an ultrasonic method, etc., a glass plate with a touch sensor function, a transparent resin plate, etc. can be used.

[0083] When a capacitive touch panel is used as the cover plate 14, a front transparent plate made of glass or a transparent resin plate is preferably provided on the side closer to the visible side than the touch panel. In this case, the transparent adhesive 13 joining the cover plate 14 and the polarizing film laminate 12 is provided with an ITO layer (not shown) which is a component of the capacitive touch sensor.

[0084] 1-3. Transparent adhesive

[0085] As transparent adhesives 11, 13, and 16, various adhesives such as those disclosed in Japanese Patent No. 6071459 can be suitably used. For example, a (meth) acrylic adhesive can be used, and a curing adhesive that does not contain (meth) acrylic acid can also be used. As an example of the latter, an isoprene-based UV-curing adhesive can be suitably used. In addition to isoprene, the isoprene-based UV-curing adhesive can also contain an isoprene derivative as a monomer component. The adhesive can also contain monomer components other than isoprene monomers. As a monomer component, a (meth) acrylic acid derivative such as (meth) acrylic acid ester can be contained. It should be noted that in order to suppress the reduction in transmittance caused by the polyeneization of polyvinyl alcohol, it is effective to reduce the content of the acid component in the transparent adhesives 11, 13, and 16.

[0086] 2. Polarizing film laminate

[0087] The polarizing film laminate 12 includes at least a polarizing film 120 and a polarizing film protective film 121 bonded to at least one side, for example, the visible side, of the polarizing film 120. As in the present embodiment, polarizing film protective films 121 and 122 may be bonded to both sides of the polarizing film 120, that is, the visible side and the side opposite to the visible side of the polarizing film 120, respectively, via an appropriate adhesive (not shown). Although not particularly shown, other optical films may be provided between the polarizing film 120 and the polarizing film protective films 121 and 122.

[0088] In order to comprehensively solve the problems that occur in high temperature or high humidity environments, especially the problems of "polyeneization", "discoloration" and "heat reddening", the present invention particularly focuses on the iodine concentration (wt.%) of the polarizing film 120 and the moisture content (g / m 2 ). These values ​​can be adjusted, for example, during the manufacture of a polarizing film or a polarizing film laminate.

[0089] 2-1.Polarizing film

[0090] Polarizing film 120 is made of a polyvinyl alcohol (PVA) resin film containing iodine. As a material suitable for PVA-type films of polarizing film, PVA or its derivatives can be used. As derivatives of PVA, in addition to polyvinyl formal, polyvinyl acetal, etc., derivatives modified by olefins such as ethylene and propylene, unsaturated carboxylic acids such as acrylic acid, methacrylic acid, crotonic acid, or their alkyl esters, acrylamide, etc. can also be listed. PVA generally uses PVA with a degree of polymerization of about 1000 to 10000 and a saponification degree of about 80 to 100 mol%. PVA-type films made of these materials tend to contain moisture easily.

[0091] The PVA film may also contain additives such as plasticizers. Examples of the plasticizer include polyols and condensates thereof, such as glycerol, diglycerol, triglycerol, ethylene glycol, propylene glycol, and polyethylene glycol. The amount of the plasticizer is not particularly limited, but is preferably 20% by weight or less in the PVA film.

[0092] 2-1-1. Manufacturing of polarizing film

[0093] When manufacturing a polarizing film having a thickness of 6 μm or more, for example, a dyeing treatment of dyeing the PVA film with iodine and a stretching treatment of stretching the PVA film in at least one direction are performed. Generally, a series of treatments including swelling, dyeing, cross-linking, stretching, washing and drying can be performed on the PVA film.

[0094] The swelling treatment can be performed, for example, by immersing the PVA film in a swelling bath (water bath). By this treatment, the PVA film can be swollen while cleaning the dirt and anti-blocking agent on the surface of the PVA film, thereby preventing uneven dyeing and the like. Glycerin, potassium iodide, etc. can also be appropriately added to the swelling bath. The temperature of the swelling bath is, for example, about 20 to 60° C., and the immersion time in the swelling bath is, for example, about 0.1 to 10 minutes.

[0095] The dyeing treatment can be performed, for example, by immersing the PVA film in an iodine solution. The iodine solution is usually an iodine aqueous solution, which contains potassium iodide as iodine and a dissolving aid. The iodine concentration is, for example, about 0.01 to 1% by weight, preferably 0.02 to 0.5% by weight. The potassium iodide concentration is, for example, about 0.01 to 10% by weight, preferably 0.02 to 8% by weight.

[0096] During the dyeing treatment, the temperature of the iodine solution is, for example, about 20 to 50° C., preferably 25 to 40° C. The immersion time is, for example, about 10 to 300 seconds, preferably 20 to 240 seconds. During the iodine dyeing treatment, the concentration of the iodine solution, the immersion temperature of the PVA film in the iodine solution, the immersion time, and other conditions are adjusted so that the iodine content and potassium content in the PVA film are within the above ranges.

[0097] The cross-linking treatment can be carried out, for example, by immersing the PVA film after iodine dyeing in a treatment bath containing a cross-linking agent. As a cross-linking agent, any appropriate cross-linking agent can be used. As specific examples of cross-linking agents, boric compounds such as boric acid and borax, glyoxal, glutaraldehyde, etc. can be cited. These cross-linking agents can be used alone or in combination. As a solvent for the solution of the cross-linking bath, water is usually used, but an organic solvent compatible with water can also be appropriately added. Relative to 100 parts by weight of the solvent, the cross-linking agent is used in a ratio of, for example, 1 to 10 parts by weight. Preferably, the solution of the cross-linking bath further contains an auxiliary agent such as iodide. The concentration of the auxiliary agent is preferably 0.05 to 15% by weight, and more preferably 0.5 to 8% by weight. The temperature of the cross-linking bath is, for example, about 20 to 70°C, and preferably 40 to 60°C. The immersion time in the cross-linking bath is, for example, about 1 second to 15 minutes, and preferably 5 seconds to 10 minutes.

[0098] Stretching treatment is a treatment in which the PVA film is stretched in at least one direction. Generally speaking, the PVA film is uniaxially stretched in the conveying direction (length direction). There is no particular limitation on the stretching method, and any method of wet stretching method and dry stretching method can be adopted. In the case of wet stretching method, the PVA film is stretched to a given ratio in a treatment bath. As a solution of the stretching bath, a solution obtained by adding compounds necessary for various treatments to solvents such as water or organic solvents (such as ethanol) can be appropriately used. As a dry stretching method, for example, an inter-roll stretching method, a heated roller stretching method, a compression stretching method, etc. can be cited. In the manufacture of polarizing film, stretching treatment can be carried out in any stage. Specifically, it can be carried out simultaneously with swelling, dyeing, and cross-linking, or it can be carried out at any time before and after the above-mentioned treatments. In addition, stretching can also be carried out in multiple stages. The cumulative stretching ratio of the PVA film is, for example, more than 5 times, preferably about 5 to 7 times.

[0099] The PVA-based film (stretched film) subjected to the above-mentioned respective treatments is subjected to water washing treatment and drying treatment according to a conventional method.

[0100] The water washing treatment can be carried out, for example, by immersing the PVA film in a water washing bath. The water washing bath can be pure water or an aqueous solution of an iodide (e.g., potassium iodide, sodium iodide, etc.). The concentration of the iodide aqueous solution is preferably 0.1 to 10% by weight. An auxiliary agent such as zinc sulfate or zinc chloride can also be added to the iodide aqueous solution.

[0101] The water washing temperature is, for example, 5 to 50° C., preferably 10 to 45° C., and more preferably 15 to 40° C. The immersion time is, for example, about 10 to 300 seconds, preferably 20 to 240 seconds. The water washing treatment may be performed only once, or may be performed multiple times as needed. When multiple water washing treatments are performed, the type and concentration of the additives contained in the water washing bath used for each treatment may be appropriately adjusted.

[0102] The drying treatment of the PVA-based film can be performed by any appropriate method (for example, natural drying, air drying, and heat drying).

[0103] 2-1-2. Manufacturing of polarizing film

[0104] Polarizing films with a film thickness of less than 6 μm can be manufactured, for example, by the manufacturing method disclosed in Japanese Patent Gazette No. 4751481. The manufacturing method includes: a laminate preparation process in which a PVA-type resin layer is formed on a thermoplastic substrate; a stretching process in which the PVA-type resin layer and the thermoplastic resin substrate are stretched integrally; a dyeing process in which a dichroic substance is adsorbed on the PVA resin layer, and the like. Insolubilization treatment and cross-linking treatment, drying treatment, cleaning treatment, and the like of the PVA-type resin layer can also be adopted as needed. The stretching treatment can be implemented before or after the dyeing treatment. In addition, any stretching method of stretching in a gas atmosphere and stretching in an aqueous solution such as a boric acid aqueous solution can be adopted. In addition, the stretching can be a one-stage stretching or a multi-stage stretching of more than two stages.

[0105] Reference Figure 2 Here, an example of a method for producing a polarizing film is described. Here, a PVA-based resin layer formed on a resin substrate is stretched integrally with the resin substrate to produce a polarizing film.

[0106] [Laminate production process (A)]

[0107] First, a non-crystalline ester thermoplastic resin substrate with a glass transition temperature of 75°C and a thickness of 200 μm, for example, isophthalic acid copolymerized polyethylene terephthalate (hereinafter referred to as "non-crystalline PET") 6 with 6 mol% of isophthalic acid, and a 4-5 wt% PVA aqueous solution obtained by dissolving PVA powder with a polymerization degree of 1000 or more and a saponification degree of 99% or more in water are prepared. Next, in a laminate production device 20 having a coating mechanism 21, a drying mechanism 22, and a surface modification treatment device 23, the PVA aqueous solution is coated on the non-crystalline PET substrate 6, and dried at a temperature of 50-60°C, and a PVA layer 2 with a glass transition temperature of 80°C and a thickness of 7 μm is formed on the PET substrate 6. In this way, a laminate 7 including a 7 μm thick PVA layer can be produced. At this time, by corona-treating the surface of the amorphous PET substrate 6 using the surface modification treatment device 23, the adhesion between the amorphous PET substrate 6 and the PVA layer 2 formed thereon can be improved.

[0108] Next, the laminate 7 including the PVA layer was subjected to the following treatment including two-step stretching treatment of auxiliary stretching in an air atmosphere and stretching in a boric acid aqueous solution, thereby finally producing a polarizing film having a thickness of 3 μm.

[0109] [Assisted stretching treatment in gas atmosphere (B)]

[0110] In the first stage of the in-air auxiliary stretching treatment (B), the laminate 7 including the 7 μm thick PVA layer 2 is stretched integrally with the PET substrate 6 to generate a "stretched laminate 8" including the 5 μm thick PVA layer 2. Specifically, in the in-air auxiliary stretching treatment device 30 equipped with a stretching mechanism 31 in the oven 33, the laminate 7 including the 7 μm thick PVA layer 2 is placed in the stretching mechanism 31 of the oven 33 set to a stretching temperature environment of 130°C, and the free-end uniaxial stretching is performed in such a way that the stretching ratio reaches 1.8 times to generate the stretched laminate 8. In this stage, the roll 8' of the stretched laminate 8 can be manufactured by the winding device 32 also provided in the oven 30.

[0111] [Dyeing treatment (C)]

[0112] Next, by dyeing treatment (C), a colored laminate 9 is produced in which iodine, which is a dichroic substance, is adsorbed on a 5 μm thick PVA layer 2 in which PVA molecules are oriented. Specifically, in a dyeing device 40 having a dye bath 42 of a dyeing liquid 41, a stretched laminate 8 is continuously unloaded from a continuous unloading device 43 equipped with a roll 8' provided in the dyeing device 40, and is immersed in a dyeing liquid 41 containing iodine and potassium iodide at a liquid temperature of 30° C. for an arbitrary period of time, and the monomer transmittance of the PVA layer constituting the polarizing film finally produced is made to be 40 to 44%, thereby producing a colored laminate 9 in which iodine is adsorbed on the oriented PVA layer 2 of the stretched laminate 8.

[0113] In this treatment, in order to prevent the dyeing liquid 41 from dissolving the PVA layer 2 contained in the stretched laminate 8, water is used as a solvent and the iodine concentration is set to 0.30 wt%. In addition, the concentration of potassium iodide in the dyeing liquid 41 for dissolving iodine in water is set to 2.1 wt%. The ratio of the concentration of iodine to potassium iodide is 1 to 7. More specifically, the stretched laminate 8 is immersed in the dyeing liquid 41 with an iodine concentration of 0.30 wt% and a potassium iodide concentration of 2.1 wt% for 60 seconds, thereby generating a colored laminate 9 in which iodine is adsorbed on the PVA layer 2 with a thickness of 5 μm after the PVA molecules are oriented.

[0114] [Stretching treatment in a boric acid aqueous solution (D)]

[0115] The colored laminate 9 including the iodine-oriented PVA layer 2 is further stretched by the second stage of the boric acid aqueous solution stretching treatment, thereby generating an optical film laminate 60 including a 3 μm thick PVA layer constituting a polarizing film and oriented with iodine. Specifically, in the boric acid aqueous solution stretching treatment device 50 having a boric acid bath 52 of the boric acid aqueous solution 51 and a stretching mechanism 53, the colored laminate 9 continuously discharged from the dyeing device 40 is immersed in the boric acid aqueous solution 51 containing boric acid and potassium iodide and set to a stretching temperature environment of 65°C. Next, the free-end uniaxial stretching is performed in the stretching mechanism 53 provided in the boric acid aqueous solution treatment device 50 so as to achieve a stretching ratio of 3.3 times, thereby generating an optical film laminate 60 including a 3 μm thick PVA layer.

[0116] [Cleaning treatment (G)]

[0117] Next, the optical film laminate 60 including the polarizing film is preferably directly sent to the cleaning process (G). The purpose of the cleaning process (G) is to wash away the unnecessary residues attached to the surface of the polarizing film by the cleaning liquid 81 of the cleaning device 80. However, the cleaning process (G) can also be omitted, and the optical film laminate 60 including the polarizing film taken out can be directly sent to the drying process (H).

[0118] [Drying treatment (H)]

[0119] The cleaned optical film laminate 60 is sent to a drying process (H) and dried there. Next, the dried optical film laminate 60 is rolled up into a continuous web of optical film laminate 60 by a winding device 91 provided together with the drying device 90, thereby generating a roll of the optical film laminate 60 including the polarizing film. As the drying process (H), any appropriate method may be adopted, such as natural drying, air drying, and heating drying. For example, in the drying device 90 of the oven, hot air at 60°C is used for drying for 240 seconds.

[0120] 2-1-3. Others

[0121] The polarizing film preferably contains zinc. By making the polarizing film contain zinc, there is a tendency to suppress the decrease in transmittance and hue degradation of the polarizing film laminate after the heating test. When the polarizing film contains zinc, the content of zinc in the polarizing film is preferably 0.002 to 2% by weight, and more preferably 0.01 to 1% by weight.

[0122] Preferably, the polarizing film further contains sulfate ions. By making the polarizing film contain sulfate ions, there is a tendency to suppress the decrease in the transmittance of the polarizing film laminate after the heating test. In the case where the polarizing film contains sulfate ions, the content of sulfate ions in the polarizing film is preferably 0.02 to 0.45 weight%, more preferably 0.05 to 0.35 weight%, and further preferably 0.1 to 0.25 weight%. It should be noted that the content of sulfate ions in the polarizing film can be calculated based on the sulfur atom content.

[0123] In order to include zinc in the polarizing film, it is preferred to perform zinc impregnation treatment in the production process of the polarizing film. In addition, in order to include sulfate ions in the polarizing film, it is preferred to perform sulfate ion treatment in the production process of the polarizing film.

[0124] The zinc impregnation treatment can be carried out, for example, by immersing the PVA film in a zinc salt solution. As the zinc salt, an inorganic chlorine compound in an aqueous solution of zinc halides such as zinc chloride and zinc iodide, zinc sulfate, zinc acetate, etc. is preferred. In addition, various zinc complexes can also be used in the zinc impregnation treatment. In addition, when the zinc salt solution uses an aqueous solution containing potassium ions and iodide ions using potassium iodide, etc., it is easy to impregnate the zinc ions, so it is preferred. The potassium iodide concentration in the zinc salt solution is preferably set to about 0.5 to 10% by weight, and more preferably set to 1 to 8% by weight.

[0125] Sulfate ion treatment can be performed, for example, by immersing the PVA film in an aqueous solution containing a metal sulfate. As the metal sulfate, the following metal sulfate is preferred: it is easy to separate into sulfate ions and metal ions in the treatment solution, and it is easy to introduce the metal sulfate into the PVA film in the form of ions. For example, as the type of metal forming the metal sulfate, alkali metals such as sodium and potassium; alkaline earth metals such as magnesium and calcium; and transition metals such as cobalt, nickel, zinc, chromium, aluminum, copper, manganese, and iron can be listed.

[0126] In the manufacture of polarizing film, the above-mentioned zinc impregnation treatment and sulfate ion treatment can be carried out at any stage. That is, the zinc impregnation treatment and sulfate ion treatment can be carried out before the dyeing treatment or after the dyeing treatment. The zinc impregnation treatment and sulfate ion treatment can also be carried out simultaneously. Preferably, zinc sulfate is used as the above-mentioned zinc salt and the above-mentioned metal sulfate salt, and the PVA-type film is immersed in a treatment bath containing zinc sulfate, so that the zinc impregnation treatment and the sulfate ion treatment are carried out simultaneously. In addition, the above-mentioned zinc salt and the above-mentioned metal sulfate salt can also be coexisted in the dyeing solution in advance, and the zinc impregnation treatment and / or sulfate ion treatment can be carried out simultaneously with the dyeing treatment. The zinc impregnation treatment and the sulfate ion treatment can also be carried out simultaneously with the stretching.

[0127] 2-2. Polarizing film protective film

[0128] As materials constituting the polarizing film protective films 121 and 122, for example, thermoplastic resins having excellent transparency, mechanical strength, and thermal stability can be cited. Specific examples of such thermoplastic resins include cellulose resins such as triacetyl cellulose, polyester resins, polyethersulfone resins, polysulfone resins, polycarbonate resins, polyamide resins, polyimide resins, polyolefin resins, (meth)acrylic resins, cyclic polyolefin resins (norbornene resins), polyarylate resins, polystyrene resins, PVA resins, and mixtures thereof.

[0129] The polarizing film protective film may also function as a phase difference film.

[0130] The thickness of the polarizing film protective film can be appropriately adjusted for the purpose of adjusting the moisture content of the polarizing film laminate, and is preferably about 1 to 500 μm, more preferably 2 to 300 μm, and even more preferably 5 to 200 μm in view of strength, workability such as handling, and thinness.

[0131] The polarizing film protective film may contain one or more optional additives, such as ultraviolet absorbers, antioxidants, lubricants, plasticizers, mold release agents, anti-coloring agents, flame retardants, nucleating agents, antistatic agents, pigments, colorants, etc.

[0132] 2-3. Other optical films

[0133] The polarizing film and the polarizing film protective film may also be directly bonded, but may also be laminated with other optical films. For other optical films, there is no particular limitation, and for example, phase difference films, viewing angle compensation films, etc. may be used. The phase difference film as other optical films may be a film having a function as a protective film.

[0134] As described above, the polarizing film protective film may also have the function of a phase difference film, but in this case, the phase difference film as other optical films may be omitted. On the other hand, in the case where the polarizing film protective film also has the function of a phase difference film, a phase difference film may also be provided as other optical films. In this case, it substantially includes two or more layers of phase difference films.

[0135] 2-4. Adhesive

[0136] The polarizing film 120 and the polarizing film protective films 121 and 122 may be bonded together, or other optical films such as a retardation film and these films may be bonded together using, for example, a radical polymerization curable adhesive, a cationic polymerization curable adhesive, or a water-based adhesive.

[0137] (Free radical polymerization curing adhesive)

[0138] The above-mentioned free radical polymerization curable adhesive contains a free radical polymerizable compound as a curable compound. The free radical polymerizable compound can be a compound that is cured by active energy rays or a compound that is cured by heat. Examples of active energy rays include electron beams, ultraviolet rays, and visible light.

[0139] As the above-mentioned free radical polymerizable compound, for example, a compound having a free radical polymerizable functional group having a carbon-carbon double bond such as a (meth)acryloyl group and a vinyl group can be cited. As the free radical polymerizable compound, a polyfunctional free radical polymerizable compound is preferably used. The free radical polymerizable compound can be used alone or in combination of two or more. In addition, a polyfunctional free radical polymerizable compound and a monofunctional free radical polymerizable compound can also be used in combination.

[0140] As the above-mentioned polymerizable compound, preferably use the compound with high logP value (octanol / water partition coefficient), as the free radical polymerizable compound, preferably use the compound with high logP value.Herein, logP value is the index of the lipophilicity of the characterization substance, and represents the logarithm value of the partition coefficient of octanol / water.High logP value means lipophilicity, that is, means low water absorption.The logP value can be measured (flask penetration method recorded in JIS-Z-7260), and can also be calculated by calculation based on the structure of each compound as the constituent component (curable component, etc.) of the curing adhesive (ChemDraw Ultra manufactured by Cambridge Soft).

[0141] The logP value of the radical polymerizable compound is preferably 2 or more, more preferably 3 or more, and particularly preferably 4 or more. Within such a range, deterioration of the polarizer due to moisture can be prevented, and a polarizing film having excellent durability under high temperature and high humidity can be obtained.

[0142] Examples of the polyfunctional radical polymerizable compound include tripropylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol diacrylate, 2-ethyl-2-butylpropylene glycol di(meth)acrylate, bisphenol A di(meth)acrylate, bisphenol A ethylene oxide adduct di(meth)acrylate, bisphenol A propylene oxide adduct di(meth)acrylate, bisphenol A diglycidyl ether di(meth)acrylate, neopentyl glycol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, cyclic trimethylolpropane formal(meth)acrylate, dimethacrylate, and bisphenol A diglycidyl ether di(meth)acrylate. Esterification products of (meth)acrylates and polyols such as alkanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and EO-modified diglycerol tetra(meth)acrylate; 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene; epoxy (meth)acrylate; urethane (meth)acrylate; polyester (meth)acrylate, etc.

[0143] Among the above-mentioned multifunctional free radical polymerizable compounds, those with high logP values ​​are preferred. Examples of such compounds include alicyclic (meth)acrylates such as tricyclodecane dimethanol di(meth)acrylate (logP=3.05) and isobornyl (meth)acrylate (logP=3.27); long-chain aliphatic (meth)acrylates such as 1,9-nonanediol di(meth)acrylate (logP=3.68) and 1,10-decanediol diacrylate (logP=4.10); polybranched (meth)acrylates such as hydroxypivalic acid neopentyl glycol (meth)acrylate adduct (logP=3.35) and 2-ethyl-2-butylpropylene glycol di(meth)acrylate (logP=3.92); (Meth)acrylates containing aromatic rings, such as bisphenol A di(meth)acrylate (logP=5.46), bisphenol A ethylene oxide 4 mole addition product di(meth)acrylate (logP=5.15), bisphenol A propylene oxide 2 mole addition product di(meth)acrylate (logP=6.10), bisphenol A propylene oxide 4 mole addition product di(meth)acrylate (logP=6.43), 9,9-bis[4-(2-(meth)acryloyloxyethoxy)phenyl]fluorene (logP=7.48), and p-phenylphenol (meth)acrylate (logP=3.98).

[0144] When a multifunctional free radical polymerizable compound and a monofunctional free radical polymerizable compound are used in combination, the content ratio of the multifunctional free radical polymerizable compound is preferably 20 to 97% by weight, more preferably 50 to 95% by weight, further preferably 75 to 92% by weight, and particularly preferably 80 to 92% by weight relative to the total amount of the free radical polymerizable compound. If it is within such a range, a polarizing film having excellent durability under high temperature and high humidity can be obtained.

[0145] Examples of the monofunctional radical polymerizable compound include (meth)acrylamide derivatives having a (meth)acrylamide group. When a (meth)acrylamide derivative is used, a pressure-sensitive adhesive layer having excellent adhesiveness can be formed with high productivity. Specific examples of (meth)acrylamide derivatives include N-alkyl (meth)acrylamide derivatives such as N-methyl (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N-isopropyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-hexyl (meth)acrylamide; N-hydroxyalkyl (meth)acrylamide derivatives such as N-hydroxymethyl (meth)acrylamide, N-hydroxyethyl (meth)acrylamide, and N-hydroxymethyl-N-propane (meth)acrylamide; N-aminoalkyl (meth)acrylamide derivatives such as aminomethyl (meth)acrylamide and aminoethyl (meth)acrylamide; N-alkoxy (meth)acrylamide derivatives such as N-methoxymethylacrylamide and N-ethoxymethylacrylamide; N-mercaptoalkyl (meth)acrylamide derivatives such as mercaptomethyl (meth)acrylamide and mercaptoethyl (meth)acrylamide, and the like. In addition, as heterocyclic (meth)acrylamide derivatives in which the nitrogen atom of the (meth)acrylamide group forms a heterocyclic ring, for example, N-acryloylmorpholine, N-acryloylpiperidine, N-methacryloylpiperidine, N-acryloylpyrrolidine, etc. can be used. Among these, N-hydroxyalkyl (meth)acrylamide derivatives are preferred, and N-hydroxyethyl (meth)acrylamide is more preferred.

[0146] In addition, as the above-mentioned monofunctional free radical polymerizable compound, a (meth)acrylic acid derivative having a (meth)acryloyloxy group can be used; a carboxyl group-containing monomer such as (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, isocrotonic acid, etc.; a lactam vinyl monomer such as N-vinylpyrrolidone, N-vinyl-ε-caprolactam, methylvinylpyrrolidone, etc.; vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyl Vinyl monomers having a nitrogen-containing heterocyclic ring such as oxazole and vinyl morpholine, etc.

[0147] When a multifunctional free radical polymerizable compound and a monofunctional free radical polymerizable compound are used in combination, the monofunctional free radical polymerizable compound is preferably contained in an amount of 3 to 80% by weight, more preferably 5 to 50% by weight, further preferably 8 to 25% by weight, and particularly preferably 8 to 20% by weight relative to the total amount of the free radical polymerizable compound. If it is within such a range, a polarizing film having excellent durability under high temperature and high humidity can be obtained.

[0148] The above-mentioned free radical polymerization curing adhesive may further contain other additives. In the case where the free radical polymerization curing adhesive contains a curable compound cured by active energy rays, the adhesive may further contain, for example, a photopolymerization initiator, a photoacid generator, a silane coupling agent, etc. In addition, in the case where the free radical polymerization curing adhesive contains a curable compound cured by heat, the adhesive may further contain a thermal polymerization initiator, a silane coupling agent, etc. In addition, as other additives, for example, an inhibitor, a polymerization initiation aid, a leveling agent, a wettability improver, a surfactant, a plasticizer, an ultraviolet absorber, an inorganic filler, a pigment, a dye, etc. can be cited.

[0149] (Cationic polymerization curing adhesive)

[0150] The above-mentioned cationic polymerization curing adhesive contains a cationic polymerizable compound as a curable compound. As the cationic polymerizable compound, for example, a compound having an epoxy group and / or an oxetane group can be cited. The compound having an epoxy group is preferably a compound having at least two epoxy groups in the molecule. As the compound having an epoxy group, for example, a compound having at least two epoxy groups and at least one aromatic ring (aromatic epoxy compounds), a compound having at least two epoxy groups in the molecule and at least one of which is formed between two adjacent carbon atoms constituting an alicyclic ring (alicyclic epoxy compounds), etc. can be cited.

[0151] Preferably, the above-mentioned cationic polymerization curing adhesive contains a photocationic polymerization initiator. The photocationic polymerization initiator generates cationic species or Lewis acid by irradiation with active energy rays such as visible light, ultraviolet rays, X-rays, electron beams, etc., thereby initiating the polymerization reaction of epoxy groups and oxetane groups. In addition, the cationic polymerization curing adhesive may further contain the above-mentioned additives.

[0152] (Water-based adhesive)

[0153] As the aqueous adhesive, for example, aqueous solutions (for example, having a solid content concentration of 0.5 to 60% by weight) of aqueous adhesives such as isocyanate adhesives, PVA adhesives, gelatin adhesives, vinyl latex adhesives, and aqueous polyester adhesives can be preferably used.

[0154] The adhesive may be applied to any one of the polarizing film 120, the polarizing film protective films 121, 122, and other optical films, or to any two of them. Generally, it is preferred to immerse the polarizing film in an aqueous adhesive solution and then laminate it with the polarizing film protective films 121, 122 by a roll laminator or the like. The thickness of the adhesive layer is not particularly limited, and is, for example, about 30 nm to 1000 nm in thickness after drying.

[0155] After laminating the polarizing film, the polarizing film protective film, and other optical films with an adhesive, the laminate is subjected to a drying process. In the drying process of the laminate, in addition to the purpose of drying and solidifying the adhesive, it is also carried out for the purpose of reducing the moisture content of the polarizing film laminate to improve the initial optical properties. As a drying method, heating drying is generally used. As drying conditions, the range of 50 to 95°C is preferred, and the range of 60 to 85°C is more preferred.

[0156] The drying conditions of the laminate are not particularly limited, but in consideration of treatment efficiency and practicality, the drying temperature is preferably 50° C. or higher, and in view of making the optical properties of the polarizing film laminate uniform, it is preferably 95° C. or lower. The drying temperature may be increased stepwise within the above temperature range.

[0157] The drying of the laminate can be carried out continuously with the bonding process of the polarizing film, the polarizing film protective film, and other optical films. In addition, after the laminate of the polarizing film, the polarizing film protective film, and other optical films is temporarily wound into a roll state, it can be dried as another treatment.

[0158] Generally speaking, in order to reduce the moisture content of the polarizing film laminate, high temperature / long time drying conditions are necessary. From the perspective of reducing the moisture content of the polarizing film laminate, high temperature / long time drying is preferred, but on the other hand, it sometimes causes a reduction in the optical properties of the polarizing film laminate. By using a polarizing film protective film with a small saturated water absorption and a polarizing film protective film with a high moisture permeability, the moisture content of the polarizing film laminate can be adjusted to the above-mentioned desired range even without using strict drying conditions.

[0159] 2-5. Adhesive

[0160] The adhesive described in the above-mentioned "1-3. Transparent adhesive" can be used in the same manner.

[0161] 3. Reliability evaluation project

[0162] Multiple phenomena that may occur in polarizing film laminates, namely, polyeneization, discoloration, and reddening by heating, were evaluated. The mechanism of each phenomenon is not yet clear, but it can be roughly estimated as follows.

[0163] <Polyene>

[0164] In a high temperature and high humidity environment, the single transmittance of the polarizing film laminate decreases. It is speculated that this decrease is due to the polyeneization of PVA. Polyene refers to -(CH=CH) n -, which can be formed in the polarizing film by heating. Polyene will cause the transmittance of the polarizing film to be significantly reduced. In addition, in a high temperature and high humidity environment, the PVA-polyiodine complex is destroyed and I - and I2.

[0165] The polyene formation of PVA is considered to be initiated by a dehydration reaction promoted by iodine (I2) generated in a high temperature and high humidity environment and heating as shown in the following chemical formula 1.

[0166] (Chemical formula 1)

[0167]

[0168] It is considered that the PVA-polyiodine complex present in the polarizing film is destroyed by heating, and the resulting I2 forms a charge transfer complex (HO···I2) with the OH group in PVA, and then undergoes polyeneization via the OI group.

[0169] <Decolorization>

[0170] In the iodine-dyed and stretched PVA film (polarizing film), iodine is present in the form of I3 - and I5 - The polyiodide ions of PVA form a complex (PVA polyiodide complex) with the oriented PVA. At this time, PVA forms crosslinking points through a crosslinking agent such as boric acid, thereby maintaining the orientation.

[0171] However, if the polarizing film is placed under high temperature and high humidity, the hydrolysis of the boric acid crosslinking will be induced, resulting in a decrease in the orientation of PVA and the disintegration of the PVA polyiodine complex. As a result, the visible light absorption based on the PVA polyiodine complex decreases, and the transmittance on the long wavelength side of about 700nm and the short wavelength side of about 410nm increases. In this way, discoloration in black display will occur in the polarizing film placed under high temperature and high humidity.

[0172] <Red when heated>

[0173] In the iodine-dyed and stretched PVA film (polarizing film), iodine is present in the form of I3 - and I5 - The polyiodide ion forms a complex with PVA (PVA polyiodine complex). - It has a broad absorption peak around 470nm, I5 - It has a broad absorption peak around 600nm. That is, PVA-I3 - The complex is responsible for the absorption on the short wavelength side (blue side), PVA-I5 - The complex is responsible for absorption on the long wavelength side (red side).

[0174] However, the PVA-I5 - The complex has weak resistance to heating. If the polarizing film is placed at high temperature, PVA and I5 - The complex formation of I5 - break down.

[0175] Therefore, in the polarizing film placed at high temperature, PVA-I5 responsible for absorption on the long wavelength side - As the amount of complexes decreases, the transmittance on the long wavelength side of about 700 nm increases, and the color of the polarizing film changes to red.

[0176] 4. Examples and Comparative Examples

[0177] Hereinafter, although an Example and a comparative example are demonstrated together, it is needless to say that this invention is not limited to the description in these Examples.

[0178] As examples and comparative examples, the “thickness of polarizing film (μm)”, and / or the “iodine concentration of polarizing film (wt.%)”, and / or the “water content of polarizing film laminate (g / m 2 )” samples of various polarizing film stacks with different

[0179] <Film thickness of polarizing film>

[0180] The film thickness (μm) of the polarizing film is measured using a spectroscopic film thickness meter MCPD-1000 (manufactured by Otsuka Electronics Co., Ltd.). The thickness of the polarizing film protective film is also measured using the spectroscopic film thickness meter. The polarizing film contained in the sample can be taken out by immersing the sample in a solvent and dissolving the polarizing film protective film. As the solvent, respectively, for example, when the polarizing film protective film is a cellulose triacetate resin, dichloromethane is used, when the polarizing film protective film is a cycloolefin resin, cyclohexane is used, and when the polarizing film protective film is an acrylic resin, methyl ethyl ketone is used. It should be noted that when the resin of the polarizing film protective film provided on one side of the polarizing film is different from the resin of the polarizing film protective film provided on the other side, the above-mentioned solvent is used to dissolve each resin in turn.

[0181] <Iodine concentration of polarizing film>

[0182] When producing a polarizing film, the iodine concentration (wt. %) of the polarizing film can be changed by adjusting, for example, the concentration of the iodine aqueous solution in which the PVA-based film or the PVA layer is immersed and the immersion time.

[0183] The iodine concentration of the polarizing film is measured by the following method: The polarizing film contained in the sample can be taken out by immersing the sample in a solvent and dissolving the polarizing film protective film in the same manner as when measuring the film thickness of the polarizing film.

[0184] (Fluorescence X-ray measurement)

[0185] When measuring the iodine concentration of the polarizing film, first, the iodine concentration was quantitatively determined using a calibration curve method of fluorescent X-ray analysis. A fluorescent X-ray analyzer ZSX-PRIMUS IV (manufactured by Rigaku Corporation) was used as an apparatus.

[0186] The value directly obtained by the fluorescent X-ray analyzer is not the concentration of each element, but the fluorescent X-ray intensity (kcps) of the wavelength inherent to each element. Therefore, in order to determine the iodine concentration contained in the polarizing film, it is necessary to use a calibration curve to convert the fluorescent X-ray intensity into a concentration. The iodine concentration of the polarizing film in this specification refers to the iodine concentration (wt%) based on the weight of the polarizing film.

[0187] (Preparation of calibration curve)

[0188] The calibration curve was prepared according to the following steps.

[0189] 1. A known amount of potassium iodide was dissolved in a PVA aqueous solution to prepare 7 types of PVA aqueous solutions containing iodine at known concentrations. The PVA aqueous solution was applied to polyethylene terephthalate, dried, and then peeled off to prepare samples 1 to 7 of PVA films containing iodine at known concentrations.

[0190] The iodine concentration (wt %) of the PVA film was calculated according to the following mathematical formula 1.

[0191] [Mathematical formula 1]

[0192] Iodine concentration (wt%) = {potassium iodide amount (g) / (potassium iodide amount (g) + PVA amount (g))} × (127 / 166)

[0193] (Molecular weight of iodine: 127Molecular weight of potassium: 39)

[0194] 2. For the produced PVA film, the fluorescence X-ray intensity (kcps) corresponding to iodine was measured using a fluorescence X-ray analyzer ZSX-PRIMUS IV (manufactured by Rigaku Corporation). The fluorescence X-ray intensity (kcps) was set as the peak value of the fluorescence X-ray spectrum. In addition, the film thickness of the produced PVA film was measured using a spectroscopic film thickness meter MCPD-1000 (manufactured by Otsuka Electronics Co., Ltd.).

[0195] 3. The fluorescence X-ray intensity was divided by the thickness (μm) of the PVA film to obtain the fluorescence X-ray intensity per unit thickness of the film (kcps / μm). Table 1 shows the iodine concentration and the fluorescence X-ray intensity per unit thickness of each sample.

[0196] [Table 1]

[0197]

[0198] 4. Based on the results shown in Table 1, a calibration curve was prepared with the fluorescence X-ray intensity per unit thickness of the PVA film (kcps / μm) as the horizontal axis and the iodine concentration (wt%) contained in the PVA film as the vertical axis. The prepared calibration curve is shown in Figure 3The mathematical formula for calculating the iodine concentration from the fluorescent X-ray intensity per unit thickness of the PVA film using the calibration curve is determined as shown in Mathematical Formula 2. It should be noted that, Figure 3 The R2 in is the correlation coefficient.

[0199] [Mathematical formula 2]

[0200] (iodine concentration) (wt%) = 14.474 × (fluorescent X-ray intensity per unit thickness of PVA film) (kcps / μm)

[0201] (Calculation of iodine concentration)

[0202] The fluorescent X-ray intensity per unit thickness (kcps / μm) was calculated by dividing the fluorescent X-ray intensity obtained by measuring the sample by the thickness. The fluorescent X-ray intensity per unit thickness of each sample was substituted into Formula 2 to calculate the iodine concentration.

[0203] <Water content of polarizing film laminate>

[0204] Moisture content of polarizing film laminate (g / m 2 ) can be mainly determined by adjusting the film thickness of the polarizing film, the material and thickness of the polarizing film protective film bonded to the polarizing film, etc. In addition, it can also be adjusted by cross-linking treatment (boric acid content, etc.) during the manufacture of the polarizing film.

[0205] The moisture content of the polarizing film laminate is measured by the following method.

[0206] First, the polarizing film laminated bodies obtained in Examples and Comparative Examples were cut into a square of 0.1 m×0.1 m.

[0207] Put the cut samples into a thermostat and humidity chamber and place them in an environment with a temperature of 23°C and a relative humidity of 55% for 48 hours. Then, take out the samples in a clean room with the same environment as that in the thermostat, i.e., a temperature of 23°C and a relative humidity of 55%, and measure the weight within 5 minutes after taking them out. The sample weight at this time is set as the initial weight W1 (g). It should be noted that as long as it is within about 15 minutes after taking it out, even if the temperature in the clean room fluctuates by about 2°C to 3°C, and even if the relative humidity in the clean room fluctuates by about ±10%, it will not have a substantial impact on the initial weight.

[0208] Next, the sample is put into a dryer and dried at 120°C for 2 hours. Then, the dried sample is taken out in the clean room set at a temperature of 23°C and a relative humidity of about 55%, and the weight is measured within 10 minutes after taking it out. The sample weight at this time is set as the dried weight W2 (g). Different from the above, it is set to within 10 minutes instead of within 5 minutes, taking into account the cooling time. It should be noted that, as mentioned above, as long as it is within about 15 minutes after taking it out, it will not have a substantial impact on the dried weight.

[0209] The equilibrium moisture content M (g / m2) of the polarizing film laminate is calculated from the initial weight W1 and the weight W2 of the sample obtained in this way by the following formula: 2 ).

[0210] (Formula) M = (W1-W2) / (0.1×0.1)

[0211] The “water content of the polarizing film laminate” referred to in the present invention refers to the equilibrium water content calculated by the above-mentioned method.

[0212] [Example 1]

[0213] (Production of polarizing film)

[0214] As the resin substrate, a long amorphous isophthalic acid copolymer polyethylene terephthalate film (isophthalic acid group modification degree 5 mol%, thickness: 100 μm) (modification degree = isophthalic acid unit / (ethylene terephthalate unit + isophthalic acid unit)) was used. One side of the resin substrate was subjected to corona treatment (treatment conditions: 55 W·min / m 2 ), and an aqueous solution containing PVA (polymerization degree 4200, saponification degree 99.2 mol%) and 13 parts by weight of potassium iodide relative to PVA was applied to the corona treated surface at room temperature. The PVA was prepared by mixing 90 parts by weight of PVA (polymerization degree 4200, saponification degree 99.2 mol%) and 10 parts by weight of acetoacetyl-modified PVA (manufactured by Nippon Synthetic Chemical Industry Co., Ltd., trade name "GOHSEFIMER Z410"), and then dried at 60°C to form a PVA-based resin layer with a thickness of 13 μm, thereby producing a laminate.

[0215] The obtained laminate was subjected to free-end uniaxial stretching to 2.4 times in the longitudinal direction (length direction) between rolls having different peripheral speeds in an oven at 130° C. (auxiliary stretching in a gas atmosphere).

[0216] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution prepared by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).

[0217] Next, the film was immersed in a dyeing bath (an iodine aqueous solution prepared by mixing iodine and potassium iodide at a weight ratio of 1:7 per 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so as to give a predetermined transmittance (dyeing treatment).

[0218] Next, the mixture was immersed in a crosslinking bath (boric acid aqueous solution prepared by blending 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).

[0219] Then, while the laminate was immersed in a boric acid aqueous solution (boric acid concentration: 3.0 wt%) at a liquid temperature of 70°C, it was uniaxially stretched (stretched in aqueous solution) in the longitudinal direction (length direction) between rollers with different peripheral speeds so that the total stretching ratio became 5.5 times.

[0220] Then, the laminated body was immersed in a cleaning bath (an aqueous solution containing 4 parts by weight of potassium iodide per 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).

[0221] Thereafter, the sample was dried in an oven maintained at 90° C. (drying treatment) and brought into contact with a SUS metal roll maintained at a surface temperature of 75° C. for 2 seconds or more (hot roll drying treatment).

[0222] In this way, a polarizing film having a thickness of 5.4 μm was obtained on the resin substrate.

[0223] (Production of Polarizing Film Laminate)

[0224] A cycloolefin film (ZT12, 18 μm, manufactured by Japan Zeon Co., Ltd.) as a polarizing film protective film is bonded to the side of the obtained polarizing film opposite to the resin substrate using an ultraviolet curing adhesive. Specifically, the curing adhesive described below is applied in a manner such that the total thickness reaches 1.0 μm, and a roller machine is used for bonding. Then, UV light is irradiated from the cycloolefin film side to cure the adhesive. Next, the resin substrate is peeled off to obtain a polarizing film laminate comprising a cycloolefin polarizing film protective film and a polarizing film.

[0225] The details of the curable adhesive are as follows. An adhesive was prepared by mixing 40 parts by weight of N-hydroxyethyl acrylamide (HEAA), 60 parts by weight of acryloyl morpholine (ACMO) and 3 parts by weight of a photoinitiator "IRGACURE 819" (manufactured by BASF). The adhesive was applied on a polarizing film so that the thickness of the cured adhesive layer reached 1.0 μm, and ultraviolet rays were irradiated as active energy rays to cure the adhesive. For ultraviolet irradiation, a metal halide lamp enclosed in gallium was used, an irradiation device: Light HAMMER10 manufactured by Fusion UV Systems, Inc., valve: V valve, peak illuminance: 1600 mW / cm 2 , cumulative exposure 1000 / mJ / cm 2 (wavelength 380 to 440 nm), and the illuminance of ultraviolet rays was measured using the Sola-Check system manufactured by Solatell.

[0226] (Removal of polarizing film)

[0227] The polarizing film was taken out from the polarizing film laminate using cyclohexane as a solvent, and the iodine concentration of the polarizing film was measured.

[0228] [Example 2]

[0229] When the polarizing film of Example 1 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration during the dyeing process, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate.

[0230] [Example 3]

[0231] When the polarizing film of Example 1 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate. In addition, when the polarizing film laminate of Example 1 was prepared, a cycloolefin film (ZF12, 13 μm, manufactured by Japan Zeon Co., Ltd.) was bonded as the polarizing film protective film. The other conditions were the same as those of Example 1.

[0232] [Example 4]

[0233] When the polarizing film laminate of Example 1 was prepared, a triacetyl cellulose film (TJ40UL manufactured by Fuji Film Co., Ltd., thickness 40 μm) was bonded as a polarizing film protective film. In addition, when the polarizing film of Example 1 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration. The other conditions were the same as those of Example 1.

[0234] [Example 5]

[0235] When the polarizing film laminate of Example 1 was prepared, a transparent protective film (Nitto Denko Corporation) with a thickness of 40 μm formed of a modified acrylic polymer having a lactone ring structure was bonded as a polarizing film protective film. In addition, when the polarizing film of Example 1 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration. The other conditions were the same as those of Example 1.

[0236] [Example 6]

[0237] (Production of polarizing film)

[0238] A PVA film with an average degree of polymerization of 2700 and a thickness of 30 μm was stretched and transported while being dyed between rollers with different peripheral speed ratios. First, the PVA film was immersed in a 30°C water bath for 1 minute to swell the film, and then stretched 1.2 times in the transport direction. Then, it was immersed in an aqueous solution (liquid temperature 30°C) of potassium iodide (0.03 wt%) and iodine (0.3 wt%) for 1 minute, thereby being stretched to 3 times in the transport direction while being dyed (based on the unstretched film). Next, the stretched film was immersed in an aqueous solution (bath) of boric acid (4 wt%), potassium iodide (5 wt%) and zinc sulfate (3.5 wt%) for 30 seconds, while being stretched to 6 times in the transport direction (based on the unstretched film). After stretching, it was dried in an oven at 40°C for 3 minutes to obtain a 12.0 μm polarizing film.

[0239] (Production of Polarizing Film Laminate)

[0240] As an adhesive, an aqueous solution containing a polyvinyl alcohol resin containing an acetoacetyl group (average degree of polymerization 1200, saponification degree 98.5 mol%, acetoacetylation degree 5 mol%) and methylol melamine in a weight ratio of 3:1 was used. Using the adhesive, a 20 μm thick transparent protective film (Nitto Denko Corporation) formed of a modified acrylic polymer having a lactone ring structure was bonded to one side of the polarizing film using a roll laminator at a temperature of 30°C, and a 27 μm thick transparent protective film having a 2 μm thick hard coating layer (HC) formed on a 25 μm thick cellulose triacetate film (manufactured by Konica Minolta, trade name "KC2UA") was bonded to the other side, and then continued to heat at 70°C in an oven for 5 minutes to dry it, thereby obtaining a polarizing film laminate having transparent protective films bonded to both sides of the polarizing film.

[0241] The hard coat layer is formed by the following method. First, a hard coat layer forming material is prepared. The material is made as follows: a UV-curable resin monomer or oligomer with urethane acrylate as the main component is dissolved in butyl acetate, and in the obtained resin solution (DIC Corporation, trade name "UNIDIC 17-806". Solid content concentration 80% by weight), 5 parts by weight of a photopolymerization initiator (BASF Corporation, product name "IRGACURE906") and 0.01 parts by weight of a leveling agent (DIC Corporation, product name "GRANDIC PC4100") are added to the above-mentioned compounding solution in a ratio of 45:55 so that the solid content concentration in the above-mentioned solution reaches 36% by weight, thereby making a hard coat layer forming material. The hard coating forming material prepared in this way was applied to the transparent protective film so that the thickness of the hard coating after curing was 2 μm to form a coating film. Next, the film was dried at 90° C. for 1 minute and then irradiated with a high pressure mercury lamp at a cumulative light intensity of 300 mJ / cm 2 The coating film was cured by ultraviolet rays.

[0242] (Removal of polarizing film)

[0243] The polarizing film was taken out from the polarizing film laminate using dichloromethane and methyl ethyl ketone as a solvent, and the iodine concentration of the polarizing film was measured.

[0244] [Example 7]

[0245] When the polarizing film of Example 6 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration. In addition, when the polarizing film laminate of Example 6 was prepared, as a polarizing film protective film, a transparent protective film with a thickness of 30 μm formed of a modified acrylic polymer having a lactone ring structure (Nitto Denko Corporation) was bonded to one side of the obtained polarizing film, and a transparent protective film with a thickness of 49 μm formed on a cellulose triacetate film with a thickness of 40 μm (manufactured by Konica Minolta, trade name "KC4UY") with a thickness of 9 μm HC was bonded to the other side. The other conditions were the same as those of Example 6.

[0246] [Example 8]

[0247] When the polarizing film of Example 6 was prepared, a PVA film with a thickness of 45 μm was stretched and transported during the stretching process to obtain a polarizing film with a thickness of 18.0 μm. In addition, during the dyeing process, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration. In addition, when the polarizing film laminate of Example 6 was prepared, as a polarizing film protective film, a transparent protective film with a thickness of 30 μm formed of a modified acrylic polymer having a lactone ring structure (Nitto Denko Corporation) was bonded to one side of the obtained polarizing film, and a triacetyl cellulose film (TJ40UL, manufactured by Fuji Film Co., Ltd., thickness 40 μm) was bonded to the other side. The other conditions were the same as those of Example 6.

[0248] [Example 9] to [Example 14]

[0249] When the polarizing film of Example 8 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration during the dyeing process, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate.

[0250] [Comparative Example 1] to [Comparative Example 2]

[0251] When the polarizing film of Example 1 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration during the dyeing process, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate.

[0252] [Comparative Example 3]

[0253] When the polarizing film laminate of Example 1 was prepared, a cycloolefin film (ZD12, 27 μm, manufactured by Japan Zeon Co., Ltd.) was bonded as a polarizing film protective film. In addition, during the dyeing process, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate. The other conditions were the same as those of Example 1.

[0254] [Comparative Example 4]

[0255] When the polarizing film of Example 1 was prepared, the concentration of the iodine aqueous solution was changed during the dyeing process, the iodine concentration was changed by adjusting the immersion time, and the moisture content of the polarizing film laminate was changed by adjusting the thickness of the polarizing film protective film.

[0256] [Comparative Example 5]

[0257] When preparing the polarizing film of Example 1, the laminated body having a PVA-type resin layer having a thickness of 10 μm was subjected to auxiliary stretching in a gas atmosphere and stretching in an aqueous solution, thereby obtaining a polarizing film of 4.0 μm. In addition, when preparing the polarizing film laminated body of Example 1, a cycloolefin film (ZD12, 27 μm, manufactured by Japan Zeon Co., Ltd.) was bonded as a polarizing film protective film. In addition, in the dyeing process, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminated body. Regarding other conditions, it is the same as in Example 1.

[0258] [Comparative Example 6]

[0259] When the polarizing film of Example 6 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration during the dyeing process, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate.

[0260] [Comparative Example 7]

[0261] When the polarizing film of Example 7 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration during the dyeing process, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate.

[0262] [Comparative Example 8] to [Comparative Example 11]

[0263] When the polarizing film of Example 6 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration during the dyeing process, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate.

[0264] [Comparative Example 12]

[0265] When the polarizing films of Examples 8 to 14 were prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted during the dyeing process to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate. The other conditions were the same as those of Examples 8 to 14.

[0266] [Comparative Example 13]

[0267] (Production of polarizing film)

[0268] When the polarizing films of Examples 8 to 14 were prepared, a PVA film with a thickness of 60 μm was stretched and transported during the stretching process to obtain a polarizing film with a thickness of 22.0 μm. In addition, during the dyeing process, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate. The other conditions were the same as those of Examples 8 to 14.

[0269] (Production of Polarizing Film Laminate)

[0270] As a polarizing film protective film, a transparent protective film with a thickness of 30 μm formed of a modified acrylic polymer having a lactone ring structure (Nitto Denko Corporation) was bonded to one side of the obtained polarizing film, and a transparent protective film with a thickness of 49 μm formed on a 40 μm thick cellulose triacetate film (manufactured by Konica Minolta, trade name "KC4UY") with a thickness of 9 μm HC was bonded to the other side. The other treatments were the same as in Examples 8 to 14.

[0271] (Removal of polarizing film)

[0272] The conditions for taking out are the same as those in Examples 8 to 14.

[0273] [Comparative Example 14]

[0274] When the polarizing film of Comparative Example 13 was prepared, the concentration of the iodine aqueous solution and the immersion time were adjusted in the dyeing process to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate. In addition, as the polarizing film protective film, a transparent protective film with a thickness of 20 μm formed of a modified acrylic polymer having a lactone ring structure (Nitto Denko Corporation) was bonded to one side of the polarizing film. The other conditions were the same as those of Comparative Example 13.

[0275] [Comparative Example 15]

[0276] When the polarizing films of Examples 8 to 14 were prepared, a PVA film with a thickness of 75 μm was stretched and transported during the stretching process to obtain a polarizing film with a thickness of 28 μm. In addition, during the dyeing process, the concentration of the iodine aqueous solution and the immersion time were adjusted to change the iodine concentration, and the thickness of the polarizing film protective film was adjusted to change the moisture content of the polarizing film laminate. The other conditions were the same as those of Examples 8 to 14.

[0277] 4-1. Reliability test

[0278] Using the polarizing film laminate 12 obtained in the examples and comparative examples, Figure 4As shown, glass plates (slide glass manufactured by Matsunami Glass, product number: S2000423, specifications: water-edge-grinded 65×165 mm, thickness 1.3 mm) were laminated on both surfaces of a polarizing film laminate 12 via adhesives 11 and 13, respectively, and this was used as a sample.

[0279] As the adhesive, CS9868US (Nitto Denko Corporation) with a thickness of 200 μm was used on one side of the polarizing film laminate, and an acrylic adhesive (thickness of 20 μm) used for the polarizing film laminate of CRT1794YCU (Nitto Denko Corporation) was used on the other side of the polarizing film laminate. The acrylic adhesive for the other side was obtained as follows: 99 parts by weight of butyl acrylate (the same below), 1.0 part of 4-hydroxybutyl acrylate, and 0.3 part of 2,2'-azobisisobutyronitrile were added together with ethyl acetate to a reaction container equipped with a condenser, a nitrogen inlet pipe, a thermometer, and a stirring device, and reacted at 60° for 4 hours under a nitrogen stream. Ethyl acetate was then added to the reaction solution to obtain a solution containing an acrylic polymer having a weight average molecular weight of 1.65 million (solid content concentration 30% by weight), and 0.3 parts of dibenzoyl peroxide (NOF Corporation: NYPER BMT), 0.1 parts of trimethylolpropane xylene diisocyanate (Mitsui Takeda Chemicals, Inc.: Takenate D110N), and 0.2 parts of a silane coupling agent (A-100, acetoacetyl-containing silane coupling agent, manufactured by Midoriken Chemical Co., Ltd.) were added per 100 parts of the solid content of the acrylic polymer solution.

[0280] After the sample was left at 95°C for 250 hours (95°C / 250H), discoloration and reddening due to heating were evaluated. After the sample was left at 95°C for 500 hours (95°C / 500H), polyeneization was evaluated.

[0281] 4-2. Evaluation criteria

[0282] The evaluation criteria for polyene formation, red change upon heating, and discoloration are shown below.

[0283] <Polyene>

[0284] The single-body transmittance of the sample was measured before and after the 95° C. / 500 H heating test, and the change in single-body transmittance ΔTs was calculated according to the following formula.

[0285] (Formula) ΔTs=Ts 500 -Ts0

[0286] Where Ts0 is the single transmittance of the sample before heating, Ts 500 It is the single body transmittance after heating at 95℃ / 500H.

[0287] When the change ΔTs is a negative value, it is evaluated as "polyeneization (reduction in monomer transmittance)" of the sample. In other words, when the monomer transmittance after heating at 95°C / 500 hours is the same as the monomer transmittance before heating, or is greater than the monomer transmittance before heating, it is evaluated that there is no problem of polyeneization.

[0288] The single-piece transmittance of the sample was measured using a spectrophotometer (product name "DOT-3" manufactured by Murakami Color Research Laboratory Co., Ltd.) The single-piece transmittance can be determined based on JIS Z8701.

[0289] <Discoloration / Heating Reddening>

[0290] Before and after the 95°C / 250H heating test, the samples were arranged in an orthogonal Nicol manner, and the orthogonal transmittance (%) at wavelengths of 410nm and 700nm was measured by the above-mentioned spectrophotometer, and the changes ΔHs were calculated. 410 and ΔHs 700 .

[0291] The case where both of the following two conditions were satisfied was evaluated as "discoloration" of the sample.

[0292] ·Change ΔHs 410 More than 1%

[0293] ·Change ΔHs 700 More than 5%

[0294] In other words, when the change in the cross transmittance at a wavelength of 410 nm due to the heat treatment at 95° C. / 500 hours was less than 1%, and the change in the cross transmittance at a wavelength of 700 nm was less than 5%, it was evaluated that there was no problem of discoloration.

[0295] In addition, the case where the following conditions were satisfied was evaluated as the "heating reddening" of the sample.

[0296] ·Change ΔHs 410 Less than 1%

[0297] ·Change ΔHs 700 More than 5%

[0298] In other words, when the change in cross transmittance at a wavelength of 410 nm due to the heat treatment at 95° C. / 500 hours is 1% or more and the change in cross transmittance at a wavelength of 700 nm is less than 5%, it is evaluated that there is no problem of heat reddening.

[0299] The evaluation results in each of the Examples and Comparative Examples are shown in Table 2 below.

[0300] [Table 2]

[0301]

[0302] 5. Summary of evaluation results

[0303] Figure 5 The results of the examples and comparative examples are plotted in an xy orthogonal coordinate system. The x-axis (horizontal axis) represents the iodine concentration (wt.%) of the polarizing film, and the y-axis (vertical axis) represents the moisture content (g / m 2 ).

[0304] (1) According to the results of the mapping and technical common sense, it can be generally considered that when the iodine concentration is small and the water content is too small, the problem of heating red discoloration under high temperature conditions is likely to occur, and on the other hand, when the iodine concentration is large and the water content is too large, the problems of polyene and decolorization are likely to occur. In addition, it can be considered that when the iodine concentration is small and the water content is too large, the problem of decolorization under high temperature and high humidity conditions is likely to occur. In this case, as the iodine concentration increases, the problem of polyene is likely to occur. In particular, a transition region between decolorization and polyene is also observed (Comparative Examples 13 and 15).

[0305] On the other hand, it can be seen that when the iodine concentration and the water content fall within a given range, all the problems of heating red change, polyeneization and decolorization can be solved comprehensively. For example, the results of the examples are all located on the upper side of the dividing line "α", i.e., y = (1043-125x) / 240, and on the lower side of the dividing line "β", i.e., y = (379-33x) / 70, and the dividing line "α" is the periphery of the plot representing the results of Example 3 with the minimum water content, i.e., iodine concentration of 7.0 wt.% and water content of 0.7 g / m 2 The coordinate point (hereinafter referred to as the first coordinate point) and the surrounding area of ​​the plot representing the result of Example 9 with the minimum iodine concentration, that is, the iodine concentration is 2.2wt.% and the moisture content is 3.2g / m 2 The line of the coordinate point (hereinafter referred to as the second coordinate point) of the embodiment 8 having the maximum water content is drawn around the iodine concentration of 3.0wt.% and the water content of 4.0g / m 2 The coordinate point (hereinafter referred to as the fourth coordinate point) and the surrounding area of ​​the plot representing the result of Example 2 having the maximum iodine concentration, that is, the iodine concentration is 10.0wt.% and the moisture content is 0.7g / m 2 The coordinate point (hereinafter referred to as the fifth coordinate point) of the polarizing film can be obtained as a line representing the conditions necessary for comprehensively solving all problems of reddening, polyeneization and bleaching. It should be noted that these dividing lines "α" and "β" have nothing to do with the thickness of the polarizing film. In other words, they are applicable to all polarizing films with a film thickness of about 4 to 20 μm.

[0306] (2) In addition, according to the results of the mapping and technical common sense, in particular, for all polarizing films having a film thickness of about 4 to 20 μm, when the iodine concentration and the water content of the polarizing film laminate are contained in the following area, all problems of "polyeneization", "bleaching" and "heat reddening" can be solved comprehensively. The area is the area surrounded by a to e, and more specifically, the area surrounded by the iodine concentration of 7.0 wt.% and the water content of 0.7 g / m 2 The first coordinate point ("a" in the figure) and the iodine concentration are 2.2wt.% and the moisture content is 3.2g / m 2 The first line segment of the second coordinate point ("b" in the figure), connecting the second coordinate point "b" and the iodine concentration of 2.2wt.% and the moisture content of 4.0g / m 2 The second line segment of the third coordinate point ("c" in the figure), connecting the third coordinate point "c" and the iodine concentration of 3.0wt.% and the water content of 4.0g / m 2 The third line segment of the fourth coordinate point ("d" in the figure), connecting the fourth coordinate point "d" and the iodine concentration of 10.0wt.% and the water content of 0.7g / m 2 The area surrounded by the fourth line segment of the fifth coordinate point ("e" in the figure) and the fifth line segment connecting the first coordinate point "a" and the fifth coordinate point "e".

[0307] (3) Similarly, it can be seen that, especially for polarizing films having a film thickness of about 11 to 20 μm, all problems of "polyeneization", "bleaching" and "heat reddening" can be solved comprehensively when the iodine concentration and the moisture content of the polarizing film laminate are contained in the following area: the area surrounded by f, b, c, d, and g, more specifically, the area surrounded by the iodine concentration of 4.5 wt.% and the moisture content of 2.0 g / m 2 The sixth line segment connecting the sixth coordinate point ("f" in the figure) and the second coordinate point "b", the second line segment connecting the second coordinate point "b" and the third coordinate point "c", the third line segment connecting the third coordinate point "c" and the fourth coordinate point "d", the third line segment connecting the fourth coordinate point "d" and the iodine concentration of 4.5wt.% and the moisture content of 3.3g / m 2 The area surrounded by the seventh line segment connecting the seventh coordinate point ("g" in the figure) and the eighth line segment connecting the sixth coordinate point "f" and the seventh coordinate point "g".

[0308] It can be considered that, in particular, at the sixth coordinate point "f", the iodine concentration is 4.0 wt.% and the water content is 2.3 g / m 2 The coordinate point "f-1" and the seventh coordinate point "g" have an iodine concentration of 4.0wt.% and a water content of 3.5g / m 2 In the case of the coordinate point "g-1", the ideal result can be obtained.

[0309] In addition, it can be inferred that, for a polarizing film having a film thickness of about 11 to 20 μm, better results can be obtained in all aspects of "polyeneization", "bleaching" and "heat reddening" when the iodine concentration and the water content of the polarizing film laminate are contained in the following region: the region surrounded by f, b, c, d, g and divided by the line segment connecting h and i, more specifically, the region surrounded by the iodine concentration of 3.3 wt.% and the water content of 2.6 g / m 2 The ninth line segment connecting the eighth coordinate point ("h" in the figure) and the second coordinate point "b", the second line segment connecting the second coordinate point "b" and the third coordinate point "c", the third line segment connecting the third coordinate point "c" and the fourth coordinate point "d", the seventh line segment connecting the fourth coordinate point "d" and the seventh coordinate point "g", the eighth line segment connecting the sixth coordinate point "f" and the seventh coordinate point "g", and the eighth line segment connecting the eighth coordinate point "h" and the iodine concentration of 6.0wt.% and the moisture content of 2.6g / m 2 The area enclosed by the tenth line segment of the ninth coordinate point ("i" in the figure).

[0310] (4) It can be further known that, in particular, with respect to a polarizing film having a film thickness of about 4 to 11 μm, preferably a film thickness of 4 to 7 μm, and more preferably a film thickness of 4.5 to 6 μm, when the iodine concentration and the moisture content of the polarizing film stack are contained in the following area, all problems of "polyeneization", "bleaching", and "heat reddening" can be solved comprehensively. The area is an area surrounded by a, h, i, and e. More specifically, it is an area surrounded by the eleventh line segment connecting the first coordinate point "a" and the eighth coordinate point "h", the tenth line segment connecting the eighth coordinate point "h" and the ninth coordinate point "i", the twelfth line segment connecting the ninth coordinate point "i" and the fifth coordinate point "e", and the fifth line segment connecting the first coordinate point "a" and the fifth coordinate point "e".

[0311] It can be considered that, in particular, the eighth coordinate point "h" is the sixth coordinate point "f" and the ninth coordinate point "i" is the iodine concentration of 7.2 wt.% and the water content of 2.0 g / m 2 In the case of the tenth coordinate point ("j" in the figure), the ideal result can be obtained.

[0312] It can also be inferred that, for a polarizing film having a film thickness of about 4 to 11 μm, preferably a film thickness of 4 to 7 μm, and more preferably a film thickness of 4.5 to 6 μm, better results can be obtained in all aspects of "polyeneization", "bleaching" and "heat reddening" when the iodine concentration and the water content of the polarizing film laminate are contained in the following region: the region is the region surrounded by a, k, i, and e, and more specifically, the region connecting the first coordinate point "a" and the iodine concentration of 6.0 wt.% and the water content of 1.2 g / m2 The area surrounded by the thirteenth line segment connecting the eleventh coordinate point ("k" in the figure), the fourteenth line segment connecting the eleventh coordinate point "k" and the ninth coordinate point "i", the twelfth line segment connecting the ninth coordinate point "i" and the fifth coordinate point "e", and the fifth line segment connecting the first coordinate point "a" and the fifth coordinate point "e".

[0313] It can be considered that, in particular, at the eleventh coordinate point "k", the iodine concentration is 6.5 wt.% and the water content is 1.0 g / m 2 The coordinate point (k-1) and the ninth coordinate point "i" have an iodine concentration of 6.5wt.% and a water content of 2.3g / m 2 In the case of the coordinate point (i-1), a more ideal result can be obtained.

[0314] 6. Addition of anti-reflection layer

[0315] 6-1. Layer structure

[0316] In order to prevent the image quality from being degraded due to reflection of external light or reflection of images, to improve contrast, etc., an anti-reflection function such as that disclosed in Japanese Patent Application Laid-Open No. 2017-2227898 may be added. Figure 6 An example of a layer structure of a polarizing film laminate 12 to which an antireflection function is added is schematically shown in FIG. In the following description, the layer structures corresponding to the layer structures described above are denoted by the same reference numerals.

[0317] The anti-reflection function can be added by providing an anti-reflection film 200 on the visible side of the polarizing film stack 12 via an adhesive 13. The anti-reflection film 200 includes a transparent substrate 201 and an anti-reflection layer 202 disposed on the substrate. In this case, the transparent substrate 201 can also be used as a polarizing film protective film (for example, Figure 1 The polarizing film protective film 121 in the structure).

[0318] In the anti-reflection layer 202, the optical film thickness (the product of the refractive index and the thickness) of the thin film is adjusted in such a way that the reversed phases of the incident light and the reflected light cancel each other. As the material of the thin film constituting the anti-reflection layer 202, metal oxides, nitrides, fluorides, etc. can be listed. For example, as a low-refractive index material with a refractive index of 1.6 or less at a wavelength of 550nm, silicon oxide, magnesium fluoride, etc. can be listed. As a high-refractive index material with a refractive index of 1.9 or more at a wavelength of 550nm, titanium oxide, niobium oxide, zirconium oxide, tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), etc. can be listed.

[0319] The anti-reflection layer 202 may also be a single layer, but is preferably an alternating stack of a low refractive index layer and a high refractive index layer. In order to reduce reflection at the air interface, the thin film preferably provided as the outermost layer of the anti-reflection layer 202 is a low refractive index layer. As the material of the low refractive index layer and the high refractive index layer, as described above, an oxide is preferred. Among them, the anti-reflection layer 202 is preferably an alternating stack of a silicon oxide (SiO2) thin film as a low refractive index layer and a niobium oxide (Nb2O5) thin film as a high refractive index layer.

[0320] The film forming method of the thin film constituting the anti-reflection layer 202 is not particularly limited, and can be any method in a wet coating method or a dry coating method. Since a thin film having a uniform and dense film thickness can be formed, dry coating methods such as vacuum evaporation, CVD, sputtering, and electron beam evaporation are preferred. Among them, since a film with high mechanical strength is easily formed, a sputtering method is particularly preferred. By a roll-to-roll method, a long film substrate is transported in one direction (length direction) while continuous film formation is performed, thereby improving the productivity of the anti-reflection film.

[0321] In the sputtering method, a high-energy sputtering gas (such as Ar) is made to collide with a target, thereby ejecting the material from the target. Therefore, the sputtered particles also have high energy. Therefore, in the sputtering method, it is easier to form a dense film than in the vacuum evaporation method and the CVD method. Generally speaking, the moisture permeability of a thin film formed by the sputtering method is small. For example, the moisture permeability of a silicon oxide film is mostly 10g / m 2 Less than 24 hours.

[0322] By adjusting the sputtering film forming conditions, the moisture permeability can be 15g / m 2 · Thin films of more than 24 hours. For example, when the discharge voltage during sputtering is low, the kinetic energy of the sputtered particles is small, which can inhibit diffusion on the substrate surface. Therefore, the film tends to grow in a columnar shape, and the film tends to become porous. When the discharge voltage is high, the film tends to form a planar shape, and the film tends to become dense. On the other hand, when the discharge voltage becomes excessively large, the recoiled neutral particles such as Ar will damage the film surface and cause defects, so there is a tendency for the film density to decrease.

[0323] In magnetron sputtering, when the magnetic field is strong (the magnetic flux density is large), the diffusion of plasma can be suppressed, and there is a tendency for the plasma density to increase. Along with this, the discharge voltage can be reduced, so, as mentioned above, there is a tendency for the film to grow easily in a columnar shape and the moisture permeability to increase. In addition, since the kinetic energy of the sputtered particles decreases with the decrease in the discharge voltage, the damage caused by the recoil Ar particles, etc. can be reduced. Therefore, the film surface tends to become smooth, and an anti-reflection film with a small arithmetic mean roughness Ra, excellent scratch resistance, and excellent fingerprint wiping properties can be obtained. The magnetic flux density of the target surface during sputtering film formation is preferably 20mT or more, more preferably 35mT or more, further preferably 45mT or more, and particularly preferably 55mT or more.

[0324] When the pressure during film formation is high, the mean free path of the sputtered particles becomes smaller, the directivity of the sputtered particles decreases, and it becomes easy to diffuse due to Ar, so the film quality tends to become porous. On the other hand, when the film forming pressure is too high, the film forming rate decreases. In addition, when the film forming pressure is high, there is a tendency for the plasma discharge to become unstable. In order to form an oxide thin film with high moisture permeability and sufficient mechanical strength, the film forming pressure is preferably 0.4Pa to 1.5Pa.

[0325] In addition to these sputtering film forming conditions, the surface shape of the substrate that serves as the film forming base may also affect the film growth mode. For example, as mentioned above, if the surface of the transparent film substrate is subjected to plasma treatment, the sputtered film tends to grow in a columnar shape and the moisture permeability tends to increase due to the unevenness formed on the surface.

[0326] When the polarizing film laminate 12 provided with the anti-reflection layer 202 is exposed to a heated environment, the moisture in the polarizing film 120, the polarizing film protective films 121, and 122 of the polarizing film laminate 12 will evaporate to the outside. When the moisture permeability of the anti-reflection layer 202 is low, it is difficult for moisture to diffuse outside the system. For example, the transparent substrate 201 made of cellulose triacetate is easily hydrolyzed when moisture is retained inside the polarizing film laminate 12, and there is a tendency for the protective performance of the polarizing film 120 to be reduced. In addition, when cellulose acetate is hydrolyzed, free acid is generated. In the presence of acid, polyeneization of polyvinyl alcohol constituting the polarizing film 120 is likely to occur, which becomes a cause of the deterioration of the polarizing film laminate 12. In contrast, it can be considered that when the moisture permeability of the anti-reflection layer 202 is high, the moisture evaporated from the polarizing film 120 and the polarizing film protective films 121 and 122 is easy to diffuse from the surface of the anti-reflection layer 202 to the outside of the system, so that the retention of moisture can be suppressed, and the deterioration of the polarizer at high temperature can be suppressed. In particular, in the technical solution of the present application, by seeking to adjust the iodine concentration of the polarizing film and the water content of the polarizing film laminate, problems such as polyeneization are suppressed. Therefore, it is not necessary to set the moisture permeability to a very high value to fully suppress the retention of moisture.

[0327] The moisture permeability of the anti-reflection layer 202 is preferably 15 g / m 2 24h or more, more preferably 20g / m 2 24h or more, more preferably 30g / m 2 24 hours or more. From the perspective of further improving durability at high temperatures, the moisture permeability of the anti-reflection layer 202 may be 100 g / m 2 24 hours or more or 130g / m 2 24 hours or more. If the moisture permeability of the antireflection layer is too high, the durability under high humidity tends to decrease. Therefore, the moisture permeability of the antireflection layer 202 is preferably 1000 g / m 2 24h or less, more preferably 500g / m 2 Less than 24 hours.

[0328] When measuring the moisture permeability of the antireflection layer 202, the moisture permeability is measured by forming the antireflection layer 202 on the transparent substrate 201. This is because the moisture permeability of the antireflection layer 202 is a thin film, and it is difficult to obtain the moisture permeability in the form of a single body. In addition, this is because the moisture permeability of many resin films is sufficiently larger than that of the inorganic oxide layer, and therefore, the moisture permeability of the antireflection film 200 provided with the antireflection layer 202 on the transparent substrate 201 can be regarded as equal to the moisture permeability of the antireflection layer 202. In this case, the moisture permeability of the antireflection film 200 is preferably 15 to 1000 g / m 2 24h, more preferably 20 to 500 g / m 2 ·More than 24h.

[0329] 6-2. Reliability test

[0330] For Figure 6 Reliability tests were conducted on samples of the layer structure shown in . Each sample was obtained as follows: a glass plate (slide glass manufactured by Matsunami Glass, product number: S2000423, specification: water-edge polished 65×165 mm, thickness 1.3 mm) was laminated on one side of the polarizing film laminate 12 obtained in Example 11 via an adhesive 11, and an anti-reflection film 200 was laminated on the other side via an adhesive 13.

[0331] The transparent substrate 201 of the anti-reflection film 200 is a film made of cellulose triacetate with a thickness of 40 μm. The anti-reflection layer 202 composed of a single layer of SiO2 is formed on the transparent substrate 201 by sputtering. The moisture permeability of the transparent substrate 201 is changed by adjusting the sputtering film forming conditions, in other words, by adjusting the flow rate of sputtering gas such as Ar, the film forming pressure, and the film forming temperature. CS98219US (Nitto Denko Corporation) with a thickness of 250 μm is used for the adhesives 11 and 13.

[0332] 6-3. Determination of moisture permeability

[0333] The moisture permeability of the antireflection layer 202 is measured in accordance with JIS K 7129:2008 Appendix B by measuring the moisture permeability of the antireflection film 200 in a gas atmosphere at a temperature of 40° C. and a humidity of 90% RH. The moisture permeability of the transparent substrate 201 is sufficiently greater than that of the antireflection layer 202, and therefore, the moisture permeability of the entire antireflection film 200 is considered to be equal to that of the antireflection layer 202.

[0334] The evaluation results are shown in Table 3 below.

[0335] [Table 3]

[0336]

[0337] 7. Addition of phase difference layer

[0338] 7-1. Layer structure

[0339] From the viewpoint of ensuring the safety of the vehicle operator, the polarizing film laminate for the vehicle is preferably a wide viewing angle. By adding two layers of phase difference films as disclosed in Japanese Patent Publication No. 2015-111236 (double compensation) to the polarizing film laminate, and by adding a layer of one phase difference film as disclosed in Japanese Patent Publication No. 2016-148724 and Japanese Patent Publication No. 2006-72309 (single compensation), an optical display panel with improved viewing angle characteristics can be formed. Figure 7 , Figure 8 Schematic diagrams are shown of an example of a layer structure of an optical display panel obtained by adding a phase difference layer to the polarizing film laminate 12. In the following description, the layer structures corresponding to the above-described layer structures are denoted by the same reference numerals.

[0340] 7-2. Dual-chip compensation

[0341] Figure 7 The layer structure shown in is a layer structure of a liquid crystal cell 10 used in, for example, an IPS mode. The liquid crystal cell 10 includes a liquid crystal layer containing liquid crystal molecules oriented in one direction in a plane when no electric field is applied. A first polarizing film 120 is arranged on one side of the liquid crystal cell 10, that is, on the cover plate 14 side relative to the liquid crystal cell 10, and a second polarizing film 170 is arranged on the other side, that is, on the light source 18 side relative to the liquid crystal cell 10. The absorption axis of the first polarizing film 120 and the absorption axis of the second polarizing film 170 are arranged in an orthogonal manner.

[0342] The first polarizing film 120 has a protective layer (polarizing film protective film) 121 bonded to the side opposite to the first phase difference layer 212, and the first polarizing film stack 12 is formed by the first polarizing film 120 and the protective layer 121. The first polarizing film stack 12 further has another protective layer (equivalent to the first phase difference layer 212) on the same side. Figure 1 Polarizing film protective film 122), in addition, it can also be as Figure 6 As shown in FIG. 2 , an antireflection layer 202 is provided. Any polarizing film laminate in the above-mentioned Embodiments 1 to 19 can be used as the first polarizing film laminate 12 .

[0343] The second polarizing film 170 is bonded to the other side of the liquid crystal cell 10 via the adhesive layer 16. The second polarizing film 170 has a protective layer (polarizing film protective film) 171 bonded to the side opposite to the liquid crystal cell 10, and the second polarizing film laminate 17 is formed by the second polarizing film 170 and the protective layer 171. The second polarizing film 170 may further have another protective layer (polarizing film protective film) on the side on the same side as the liquid crystal cell 10. Any polarizing film laminate in the above-mentioned embodiments 1 to 14 can be used as the second polarizing film laminate 12.

[0344] In the first polarizing film stack 12 , a first retardation layer 212 and a second retardation layer 213 are arranged in this order from the first polarizing film 120 side between the first polarizing film 120 of the first polarizing film stack 12 and the liquid crystal cell 10 .

[0345] The first phase difference layer 212 is bonded to the surface of the first polarizing film 120. The second phase difference layer 213 is bonded to the surface of the first phase difference layer 212 on the opposite side to the first polarizing film 120 via the adhesive layer or adhesive layer 19. In addition, the second phase difference layer 213 is bonded to one side of the liquid crystal cell 10 via the adhesive layer or adhesive layer 11. The slow axis of the first phase difference layer 212 and the slow axis of the second phase difference layer 213 are arranged in parallel.

[0346] Examples of materials that can be used as the first phase difference layer 212 include: polycarbonate resins, polyester resins such as polyethylene terephthalate or polyethylene naphthalate, polyarylate resins, polyimide resins, cyclic polyolefin resins (polynorbornene resins), polyamide resins, polyolefin resins such as polyethylene or polypropylene, etc. Examples of preferred materials for the second phase difference layer include: acrylic resins, styrene resins, maleimide resins, and fumarate resins.

[0347] The first retardation layer 212 and the second retardation layer 213 are preferably the following combination.

[0348] 1. When the refractive index in the slow axis x direction in the plane of the first phase difference layer 212 is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer 212 satisfies the relationship of nx1>ny1>nz1, and when the refractive index in the slow axis x direction in the plane of the second phase difference layer 213 is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer 213 satisfies the relationship of nz2>nx2>ny2.

[0349] In other words, when the in-plane phase difference Re of the first phase difference layer 212 is in the range of 10nm<Re<200nm, and when the thickness of the first phase difference layer is set to d1, the thickness direction phase difference Rth represented by Rth=(nx1-nz1)×d1 is in the range of 10nm<Rth<300nm. On the other hand, when the in-plane phase difference Re of the second phase difference 213 is in the range of 10nm<Re<200nm, and when the thickness of the second phase difference layer is set to d2, the thickness direction phase difference Rth represented by Rth=(nx2-nz2)×d2 is in the range of 10nm<Rth<-300nm.

[0350] 2. When the refractive index in the slow axis x direction in the plane of the first phase difference layer 212 is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer 212 satisfies the relationship of nx1>ny1>nz1, and when the refractive index in the slow axis x direction in the plane of the second phase difference layer 213 is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer 213 satisfies the relationship of nz2>nx2=ny2.

[0351] In other words, when the in-plane phase difference Re of the first phase difference layer 212 is in the range of 10nm<Re<200nm, and when the thickness of the first phase difference layer is set to d1, the thickness direction phase difference Rth represented by Rth=(nx1-nz1)×d1 is in the range of 10nm<Rth<300nm. On the other hand, when the in-plane phase difference Re of the second phase difference 213 is in the range of 0nm<Re<10nm, and when the thickness of the second phase difference layer is set to d2, the thickness direction phase difference Rth represented by Rth=(nx2-nz2)×d2 is in the range of 10nm<Rth<-300nm.

[0352] 3. When the refractive index in the slow axis x direction in the plane of the first phase difference layer 212 is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer 212 satisfies the relationship of nz1>nx1=ny1, and when the refractive index in the slow axis x direction in the plane of the second phase difference layer 213 is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer 213 satisfies the relationship of nx2>ny2=nz2.

[0353] In other words, when the in-plane phase difference Re of the first phase difference layer 212 is in the range of 0nm<Re<10nm, and when the thickness of the first phase difference layer is set to d1, the thickness direction phase difference Rth represented by Rth=(nx1-nz1)×d1 is in the range of 10nm<Rth<300nm. On the other hand, the in-plane phase difference Re of the second phase difference 213 is in the range of 10nm<Re<200nm, and when Nz=(nx1-nz1) / (nx1-ny1) is set to, it is in the range of 1<Nz<3.

[0354] 7-3. Single chip compensation

[0355] Figure 8 The layer structure shown in Figure 7 Similarly, it can be used for example in an IPS liquid crystal cell 10. Figure 8 The substantial difference in the layer structure is that the phase difference layer 215 is provided only on one side of the liquid crystal unit 10, that is, only on the cover plate 14 side relative to the liquid crystal unit 10. The phase difference layer 215 is arranged between the first polarizing film 120 and the liquid phase unit 10. Although not specifically shown in the figure, the phase difference layer may be provided only on the light source 18 side relative to the liquid crystal unit 10, between the second polarizing film 170 and the liquid phase unit 10. Figure 7 Similarly, any polarizing film stack in the above-mentioned embodiments 1 to 19 can be used as the first polarizing film stack 12, and any polarizing film stack in the above-mentioned embodiments 1 to 14 can be used as the second polarizing film stack 17.

[0356] For the phase difference layer 215, it is preferred that when the refractive index in the slow axis x direction in the plane of the phase difference layer 215 is set to nx, the refractive index in the fast axis direction is set to ny, and the refractive index in the thickness z direction is set to nz, the phase difference layer 215 satisfies the relationship nx>nz>ny. In other words, when the in-plane phase difference Re of the phase difference layer 215 is in the range of 100nm<Re<500nm, and when the thickness of the phase difference layer is set to d1, the thickness direction phase difference Rth represented by Rth=(nx1-nz1)×d1 is preferably in the range of 10nm<Rth<300nm.

[0357] As for the thickness of the phase difference layer 215, if it is a phase difference layer formed by coating a solution that becomes a phase difference layer on a substrate such as a biaxially stretched polypropylene film and drying it, and then stretching it in the width direction while conveying it using a synchronous biaxial stretching machine and shrinking it in the MD direction, as disclosed in Japanese Patent Publication No. 2016-148724, then its thickness can be 1μm to 30μm, and more preferably 5μm to 20μm. In addition, if it is a phase difference layer formed by laminating a shrink film on both sides or one side of a polymer film that becomes a phase difference layer, and giving the polymer film a tension along the stretching direction and a shrinkage force along the direction orthogonal to the stretching direction, as disclosed in Japanese Patent Publication No. 2006-72309, then its thickness can be 30μm to 200μm, and more preferably 40μm to 150μm.

Claims

1. A polarizing film laminate, comprising: A polarizing film formed of a polyvinyl alcohol resin, and an optically transparent polarizing film protective film bonded to at least one side of the polarizing film directly or through other optical films, The polarizing film laminate is used for an optical display panel mounted on a body of a power vehicle. in, The iodine concentration (wt.%) of the polarizing film is taken as the x-axis, the moisture content (g / m 2 ) as the y-axis, the polarizing film laminate has an iodine concentration and a water content contained in the following area, which is surrounded by a first line segment connecting the first coordinate point and the second coordinate point, a second line segment connecting the second coordinate point and the third coordinate point, a third line segment connecting the third coordinate point and the fourth coordinate point, and a fourth line segment connecting the first coordinate point and the fourth coordinate point, The first coordinate point is an iodine concentration of 7.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of The second coordinate point is iodine concentration 4.5wt.% and water content 2.0g / m 2 The coordinate point of The third coordinate point is an iodine concentration of 7.2 wt.% and a moisture content of 2.0 g / m 2 The coordinate point of The fourth coordinate point is an iodine concentration of 10.0 wt.% and a water content of 0.7 g / m 2 The coordinate point of . 2 . The polarizing film laminate according to claim 1 , which has an iodine concentration and a moisture content contained in the region, and has an iodine concentration of 6.0 wt.% or less. 3 . The polarizing film laminate according to claim 1 , which has an iodine concentration and a moisture content contained in the region, and has an iodine concentration of 6.5 wt % or less.

4. The polarizing film laminate according to claim 1 or 2, wherein: The polarizing film has a thickness of 4 to 11 μm.

5. The polarizing film laminate according to claim 1 or 2, wherein: The polarizing film contains zinc.

6. The polarizing film laminate according to claim 1 or 2, wherein: For a sample composed of the polarizing film laminate and glass plates laminated on both sides of the polarizing film laminate via an adhesive, the single body transmittance after heating at 95° C. / 500 hours is the same as or greater than the single body transmittance before heating.

7. The polarizing film laminate according to claim 1 or 2, wherein: For a sample consisting of a polarizing film stack and glass plates laminated on both sides of the polarizing film stack via an adhesive, the change in orthogonal transmittance at a wavelength of 410 nm caused by a heat treatment at 95°C / 500 hours is less than 1%, and the change in orthogonal transmittance at a wavelength of 700 nm is less than 5%.

8. The polarizing film laminate according to claim 1 or 2, wherein: For a sample consisting of a polarizing film stack and glass plates laminated on both sides of the polarizing film stack via an adhesive, the change in orthogonal transmittance at a wavelength of 410 nm caused by a heat treatment at 95°C / 500 hours is greater than 1%, and the change in orthogonal transmittance at a wavelength of 700 nm is less than 5%.

9. The polarizing film laminate according to claim 1 or 2, wherein: An antireflection layer is provided on the visible side surface of the polarizing film via a substrate. The moisture permeability of the antireflection film including the substrate and the antireflection layer is 15 g / m 2 ·More than 24h.

10. An optical display panel comprising the polarizing film laminate according to any one of claims 1 to 9, the optical display panel comprising: A liquid crystal cell having a liquid crystal layer including liquid crystal molecules oriented in one direction in a plane in a state where no electric field is applied; A first polarizing film, which is disposed on one side of the liquid crystal unit; as well as A second polarizing film is disposed on the other side of the liquid crystal unit in a manner such that its absorption axis is orthogonal to the absorption axis of the first polarizing film, Between the first polarizing film and the liquid crystal unit, a first phase difference layer and a second phase difference layer are sequentially arranged from one side of the first polarizing film. When the refractive index of the first phase difference layer in the slow axis x direction within the plane is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer satisfies the relationship of nx1>ny1>nz1. When the refractive index of the second phase difference layer in the slow axis x direction within the plane is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer satisfies the relationship of nz2>nx2≥ny2.

11. An optical display panel comprising the polarizing film laminate according to any one of claims 1 to 9, the optical display panel comprising: A liquid crystal cell having a liquid crystal layer including liquid crystal molecules oriented in one direction in a plane in a state where no electric field is applied; A first polarizing film, which is disposed on one side of the liquid crystal unit; as well as A second polarizing film is disposed on the other side of the liquid crystal unit in a manner such that its absorption axis is orthogonal to the absorption axis of the first polarizing film, Between the first polarizing film and the liquid crystal unit, a first phase difference layer and a second phase difference layer are sequentially arranged from one side of the first polarizing film. When the refractive index of the first phase difference layer in the slow axis x direction within the plane is set to nx1, the refractive index in the fast axis direction is set to ny1, and the refractive index in the thickness z direction is set to nz1, the first phase difference layer satisfies the relationship nz1>nx1=ny1. When the refractive index of the second phase difference layer in the slow axis x direction within the plane is set to nx2, the refractive index in the fast axis direction is set to ny2, and the refractive index in the thickness z direction is set to nz2, the second phase difference layer satisfies the relationship nx2>ny2=nz2.

12. An optical display panel comprising the polarizing film laminate according to any one of claims 1 to 9, the optical display panel comprising: A liquid crystal cell comprising a liquid crystal layer including liquid crystal molecules oriented in one direction within a plane in a state where no electric field is applied; and A polarizing film is disposed on one side of the liquid crystal unit. A phase difference layer is arranged between the polarizing film and the liquid crystal unit. When the refractive index in the slow axis x direction within the plane of the phase difference layer is set to nx, the refractive index in the fast axis direction is set to ny, and the refractive index in the thickness z direction is set to nz, the phase difference layer satisfies the relationship nx>nz>ny.

13. An optical display panel mounted on a body of a powered vehicle, The optical display panel comprises: Optical display unit; The polarizing film laminate according to any one of claims 1 to 9, which is laminated on one surface of the optical display unit directly or via another optical film; and an optically transparent cover plate disposed along the polarizing film stack on a side of the polarizing film stack opposite to the optical display unit, The optical display unit, the polarizing film stack, and the transparent cover are bonded together by a transparent adhesive layer filled therebetween without any gaps.

14. The optical display panel according to claim 13, wherein: The transparent cover has a function of a capacitive touch sensor.

15. The optical display panel according to claim 14, wherein: An ITO layer serving as a component of a capacitive touch sensor is provided between the transparent cover plate and the polarizing film laminate.

Citation Information

Patent Citations

  • Directional control method of fold printed matter

    JP1985071459A

  • Polarizing plate and method for manufacturing the same

    JP2002090546A

  • Retardation film, process for producing same, optical film, image display device, liquid crystal panel, and liquid crystal display device

    JP2006072309A

  • Polarizing plate and image display device, and manufacturing method of those

    JP2014102353A

  • Liquid crystal panel and polarizer laminate used for liquid crystal panel

    JP2015111236A